Dramaturgia do cóccix na videoperformance Ábar - Vieira, Alba Pedreira; E. Bond, Karen (Repertório, 2021)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAakAAADPCAYAAABP9i6oAAAgAElEQVR4Aey9z+srS5bgl3+R9l54obUNWtqLxBtDLk3CLIb0Ul4JGhoxxohhQA1GQw/ywoI3qKexqih1dTl5NUl1aaac1YWmUBfoDqghH2QtcqHFMeeciMjIyDihlL76fu/33acv3CtlKjPixDknfkd8IoLO3xWapoHm2rn5unhp4KWBlwYGa+BKZcirEBmssA96kOzyIyzcI9ZPA/lqCqMogkj9GydzOFye4Wg1LOMIoskSqgeNcZiPYTQrHnz74147LCYwnj9HzvqwgGi8gPqjxG8OEEcRLA4fFuNHpexzxNMcYbXY3m1P41N1AWPBPg/5yjvY+1KsYWKVIdE4hd2x+Rz6f5YUD9rxWdE/Es45X0E8asv2aJLB7uTm889TTp82KUTRCLZnrn8igCvspiOqnLLVDk7nMxyLDaSUqATeXGadNzCKEije4Kvn/QpW+9Mj9vnQd4onVqZ1MYcomsMb1HZf2q8lFTDz4tGmxH3R/dSevh5mD9mz9akadssF7E99j7iWCwrbLXaCOn62vZuC/Gc8XcHhdIZTmcMMG6dRDOUz2rrBxHzcj4/a8eMk7MZU5ViORDBRdjkfc5hO0C5j2F+sZz9NOX2B2SiCmSVcdD2tKRGLXuF0gilWVNnOSon/63G3hDSJYTKZQJItoKzYK0/5GtJ4AuPJBNLp0twHqGAzzyCOJzCZxDBd7lUL03//uJnCdF1CVSxhPIphd1Lhb2cwGmdQ9vNtK2hTQjZJYb1dQTqZQBzHkC1z0PmGZVSyWzI2xx3Jjs/HcQLL/NyGKXxrCxQAqI+wnCakkzjJYHNgj2iOa4gnKcymKcmSpHPYH3KYpzFMULb5hnqc9QGdK4HFPCMdYRi6gDquMxiNY0iSGJLpBurmCIssofBI3mQO5YASqz7uYIp2izGsCfmBrqQuhw1k2qaolwHhlesM4mwB8yyhMON0Drohfb0UJCP6COmj0Pq8wIr0hHqOIZ3vlC9I969QrGZtWuMEVoWd2wTjSDq64R+Sb0v68flNU66pF4SFxShZwYV8IIEsTcgXtqc/i2kyPtWUMItT2KpK6rCZQ0K+mUIaj9pet5ROcsnn2tvWtC5HVnZmbEqYT+eQqxaxlNfQnydxRv5G+XOxhUO+hoTyawLLnW6gVrBbTiGecLkxW+lyA6DczDivoU6SGRSqDLJl7HwP2t3vYz07liuIk5XpHTflCibqupdHoYF8PW9lX+fUAMXyYDIak+yUN2IsizLqHFTlBlKyMeeNbLG/s9F6giyKYDzPO0kHOMEiTU2++RTlNEqoy8wxlhFTU2ZG3LWagi+bl8sJRKN5cJgOlYyZL55v4VjuIcXufryGHw5Lup8stnDE2nuMtfcUsGjK52OqyZf7Axx2XNNnu7N4v5iPIJqhoi8wx3DGSzifdzQ8Ga9KxwDOpWrhRdEE1vkBtouE5NqcrlCLMtawGEcwytZwOp9gQz3NMRxClSEAmAIFLjBDPUxmkB+PsFNxrilObPVGECVLKIoNDbHh9XS9h/0qo99WxwZoCIcKtQUcjgXMqPXD+sMhIHwnnc9hvvx7+C5B3SawPRyhzHnIZbw4OIpwL0/KVhz+nFq9EWAlpQucBG16UnGPZl4fsUM1ci13UOyXrX2uR45rPIX8WMJ2HnM6ywZOG7RHDLvjGUrlC7OiEu9XOfZIIphtCjgdC1hg2m/4KI4WbCUdBfxD8u1GNez6+pH8poZ8iUMYMWwPZ/gBh3LJB6Ywny2h+IWcJuNTDQ/3oW6qgt/PVnso9RAbDQ0H0gnPt7dte4AzzCiPRzCOU1isNnCwhpTkvAag/SZb7yFfT1k3UQybPIdliqM8XD7lMy43VlhuKP+iArjOydfmuwOcj6oMSrZd8dyrgN1lH3PsWHDvWLffanWNYxE6TZxHc/gN5dkRLPclHPMVNVomywNcqyPsdjvY73PIt+wHUbyESvV0o2wF5ekEe6UXLBsG/6kh4nlgOCxklw8tpwNlZkQVkTD3cViMIRqF50UwE2EhoQ2FLcnlpoDv8f542db82pGKL7AYRTBZHY2uD5slbIo/CvcvVuEPAOedaZVGcduKMYG5X5QzTvdqGOt6oGEJzOwkuyDjHHuR8Qz2hxPU9QVOp0ubFjcOda0LlEZVfsviAnVVQV0dqJBGp+TKZwy5UhjOt0WTlerZXWCKBXBRmefMMGm1p8y7u2AGsHV7hWO+g/yI6btCfSlhPsHWU3huTMthwleFIFZSnMFSKKsaqqqGy2FFcWMlG/qjtKRt4VDMRjCa5cBDlyOTZoCGbD2aFyquMSy3BVzqGi6nE9RXncn796tjAdtdSfpq6gqKddrxP798AR3d8g+Pb3OB49PPDyD5TYM949GCfEjrXvtAKE3ap8Cyj+u3l12mdCCnU8f5THv3dV3BfjWHeMzTB1gRU89RNeD85UEN5DemUjlCgo02NdzDQ5ljyCtu6GBjVv9xA2cKl2pPlVS62EB5rqA6n+B00SWSftr5DNg9ZI+uHbGB3ZZ9PPrB1908WpFfjGd7qJsKqrqGvSo328H1BtbUkMrgiNnsWkG+3cMZ66SmgfNhzRVxb8TLSZd9qeYdUyw0hD/Xl+ArldOhMjO67LHlkoLuUNtpoQTcaKXqgsktvvB+Z7GDcor59wU5Ya92v7Jz9u53eigsHbeKcZJ/QKvCZG7ltOa6oszhlRFbq4e2l4OZLZ7dnvTWBUpz5EKdWsvYYlb/JosC2JFT0OV9V081Fd5cSWGh1mYAaFTlmnPlasvdnHaQqlasietGJdWU2NOdtL3Da8l2oUqKezo6LP2phwJtH7G/6/TrezptHFfcGZblCqwAuJ5gkbSFWjSZQo45U7x/hlXGPUkt15AFJqKOjD/4/SNKt2Zo2KRrIetH8hu7AHN9AK5ymoxOjZzK/pZ9qeBUhaWUzvewt9YHfl6rMxyPbWF4bSrTK5rl4bxm0kgBtnkAL03l+oV7kqaxiWU3+TA2fnB4jkch2CfGsLg1h2302bd7yB59O7Z51P6tk6Y67y4o0WXCpO0A7KmXOIKdGhrFtOMQpr2YDdPWn5Yhpfn/q3NhsQ02ZnIoL41cBn5wOR0qM6OrGq7Ltk41pWphbAmH/tAYuoWIz11PW8iyJfzNX45p2M9UXsYp/kStinRrtYi2c5hvC+H+sdOTup5wIYYq+EczGj4MyWe3QOk5I4fqScXrthAyv32BY1HAucGeyRF2Kx6CmBfh1pl2TM5YEexwdeQVNdBAme+gOGIPqVv56Hc4DTXpwFRSduNBtXCWZdPRB44v47jzKF3C8YztsgbWcQTYSwn9cYYatwtaVA8TKyJtU+qbUavuAvluD8cb4/zdtLTDn9yTsuKCK6wmEfWyqtOBhoWuzQUO+zUNf6LPSfephUrDZtzjoiEWuzL3JjqgI2Nz1aa1rrUedFOo49ujBQ2Dk3mvWj8/iH5j293+juKG0mR06splet8AepipDvjCe9jbVjWnIXXyI/eYcUiedOnNa7Xjz20ewPBNJXXh1adY4ek/6kFGM7jUZygOJ7hCA+cyh0WKw4Ip90j0w+6npU/6yboO2cO2Hfv1zEyHtHZofZ+jPdMISbLm0SPMUvX5APv8SGXPacMVrF0B6UJ7usERhiv0yjE3Pd7rC5UnUbppyzh8TjV4cUpAtsvHltOhMpOWoHMtHsF0lcO5quB82FKrGsfQb5TLUNEqtIhaLtfmDEvsso4X8EfqoUWw3J/ger3AZoqOg63pK+wyrGQyKC4N1CcevovXvxfu25XUmVZ+4JxXXfNqIuydBP/0uKzuJlvX3Iv0yci9utGUe09VyfNuyxurB9oCpeTCNlvDpbnCpVDzc5uT6km1rS/zDiWizaDaaMkyh+ZawSbD3gb3eDvvqB5osuI5qHPO8xWTG5UUNCzjZLaF6lrDXs2bYSWlVwTNtiU0+Nucey56xFTSd0cuuwesbDWmuBo4qrknHNLJp+gLKRywAmyOlJmxlyjdxzhwjgJ7orgYI6NVqDcKpJCOLH9gE3CLnfQg+Paf1Iqpvn5kv+ECLaFeIlcYXR+Q0mR0aslp/DY/Q1OXPBeEQ/ahdD5o7+s5h/lsBZ5FhR030POYUTyHvDzB+VTCRs09YsPKyNwrD9wCvc0DGIGupLC3tE3bcqM5K9vT/Df7/IIWNzWQ0/xP5lSYHXGxZqdehhkdsK5DPmbbkXtyXPY1lwM1FnWv3thNRctlXgL7Uw1NVapnl/DPamogStdwupzhdDzC8XiCL7RwagQbUnwF2xnnQdoiguXpfG4WUjkp61xe1BzuZLaG4/kC9uo+HG6W7fLB5bTyT1wH4JaZap9UDbsFTuyqHgq2zGM17NJJsu/iqiaF9bsJ7EixjSn4dBd8pSuK5gh6oh5/G6UrnpQX7utho+MaJ9knoAtL3QJhQ/pkw65dO4xFT6hr3g8ky3jeL9oeGw337W7OSWk5MZ7q0N0zMplaq/aslr/9DkA71KErqTEVwqjbCWxUJdl9B6BY2baLu6u9BLWQjMWqTeN4QpmWK2LXpiOYmxVWcoCuXPb1peDJYu1jyWLPrbuqgMweqhxP4YCNZeF+XW7aOckogmTa3VMhSSfqKOgfrh60b7v3W/1IfoMjALjPCRtq+a+7velQmowOO3JeYa8qAK1PUzgGfKF6wN6mFxweRCC1n/dLZ1hrBLONXtgk5zWTRgqlzQN4qYeKaWQfK2RaQKTKmslMDSE3sJ3ZQ7Aj4ApL8oZwuRCyh23HQ1PBihZ2sDxjWtTFQ3jdNGFCumUe7iHLL1coVAPQ2JF8BOesz7BQi5nwt3GSkm7jZWl6VTjiMuTv4A4bjhLYlPpd2S6uzO9aTgfKTFVJqaReG6jrGupHdiU3PMluhvdMkDVNFLr38ecG48KurPMn3Xcee9rlFWWv626XmEJvoK5QH49GdeWFE4/o00SJYfhkMw/QFzkN3ef6V5zGvhXIQLRw4uHk9yLjtPjUwTbvx+S/zzL7wulFad14WEeCb4O675Ha7zfXKzQ0PmgJZb7enyZOTz/2cDrf395sM7/PhmUzygh+8fsEwDPCbiMO2MOxI8vjzUFtcOobPlvdUaBQ2Pc6ei9WvMFlkRR3SHdS+qT73ugH3+yXmd1KanBArwdfGnhp4KWBlwZeGnh/DbwqqffX8SuGlwZeGnhp4KWBBzXwqqQeVNzrtZcGXhp4aeClgffXwFeppJrm6pn/ef/EvmJ4aeClgZcGXhr4cWngOZWUlwxcwRJX4kyWhkaByz4Jm4TAQ1yl8vp7aeCraKCBYr0exCMMivckkjit5BSoL8H43/zjk/RgydFb1Wb99i1+vRy2sB7A9ZTT/nwbyHE98Iu3bH8gHPNKA7t5AqNxAqvNEpJb7FUAeEol5SUDE98saYkGuL5EQVPz04XQN0bu15eXBj5SA9eCjgIohi3IkiV7Ekn8IYq5LNXwX56lByvGH8uJBZbIb/jawAKXjM9vcTIDUbyDDQKx3f2Tt2y/OxTrheYAaZzBdr+BLJ4Q7Nv61fs1Gkrlxrd95GeXDIwLT4lSjaRiomsnsMovgIRg3icygjFSfhuAEBX5Ico3ko3jBObzqUVQ1oxAP9kY09UjFgdI0q4WHyF/v1XnJIMko9LBbJYRcXm20elvJS9XKaRq8y/e5Wvcf4HE+AQWi5khbCPMc79EEvsEknRGezvwncGE5oBNWA82DbwJ+gSCS5G2T7T02doAb+8jrNew0himUXo3bfpZ5HiJYj7YF99sK0cPlxKycaw2j9IGJcjGE1iVNfjspOWfoL+sl5DGU9qzpE8suMtHhLIFwxhOSMenu38SwV4qd0J52UdZR9n0/qYU81koT3pPYnBsgHvRNAlcnxagTk/opoyvcKP1jEj6eLpDBmt1GoCUH8iOyQxWyymfrBCnsKZNiSh6/9QHt2x36f2b3V+JFHjxpIvmBKtpCkmSQpqmkOKpGWoPniR3pDeN3qJy6x3lPvKzTXjWO5x7lOrmAnsiQaewK47wRSSQa7joA5RvxQfEja/b8gS52ti4PjYgk43fEJ9NO76D/P12nQdo15YO5vMZrD0b/lqqPDu7uTbvxrApClhlSHeIIEqXkCu6OuGW7iE0mzD7Nmn1wDTw3/5akTk85HxNlZ6uCzgeNrSxcYzIrgcI6+ccCe0jWOwOUDd8jtYw2vRzSOIyxfwOXzR6fdxWHT38uaWsk1dYmCDXTsWvPBT2aEIAYeNLd/iIXLa0+rhFSHcLcSyQ0XfvOZ1B+1jq5mUNXXUo681pz2SZdAmHc/UQab9jg6t8eoKbPjwRgk5aUCcLMNFnDIUC8UaeEweMHeMFFIecN0bTMPNj9P7f/kqmwPsJ6v8k6yiQj1UldZvKHSJj22TgmwRhdZAfoUe8BPL6ccq3yrgt34t3r2PBGpKLWF1GFpkk3XcUYILzneRvdpa36LyRyedKB5oi7ZPZRbaYa/Mu70bXBGpNzjbzDfcQmgM2cfUQ9AnEIRlSNsBpjYSBOXwhdNF9hHW4HmAcKZbgHWnR8mp92Dy1UP5wbeCms6WYY6E8kHD/DFvZerAqJZLXutbp1tR29INo0jIva0LvjAmhZnzpDr2GdEdxGbsLhHQPDYN0bJFdbp/OoGjsnrwMImW9geUYTxzA4b5AueHYCv0PTzAmYoRlgxAJ3PUhrthHhr6DUNz1YgX5z/+ShrK1rewTB9iObV5pwcSMovKd+mCX7a4fuHiv9prL3f5JF1/EcovJJq1sttwRB3ybyn0IkJ9b4dBWMtHZfs4UeFr7ypAacPoQ5dtkrNZrW9q2LJfJWEoWiSStRbU/3Xd1ujTOxT4DTsvyDJ2LMnp0YMuL3yWZ20KX9aedUvMb7fcGE5o98gzTAw45MZ8RfYIKq2kLO27oNNoEfvefsPd1J2GdZGobCUPTwjZ9Ozme9GixFdvCom+boXZ+yFa2HoydFC7H0r3rr5ukCzC2437ER0Jlix2ejQ1DP7bjdX2c/MVHsJdOZ1BgZbvc0XkZKyA/ZZ17IPpYnKG2avNZpRBH7IsaKquHEPWnj0+K0yd4uq7Omzr9t8sdPpOO9dceNfIIvd8uzzvhBU60kHQUkpsrKavF4ToFno+DNT7eR9o5unCX/IyHB7YsspsEYXWkAIU3iIocIFhry+hPndHMER7c0kHHC8nVTfMd8XkKfB2WYZ4Zak1L/rb1haLrdzgZLWCTdOTV+X+RyedaB55hPq2mbnwNrcKkYTznXbcQ0O/pzDSI0KzD9NjEpweEB5v1DPrdQrVyrUrqvEFmn+5J3UdY50KC37knLZwprbgeJMeTXb0Uc9cXAr5odMOVykO2ojBUehRglZmW3EDAOWRsINyyk/H1upX/Hr3Kfo5sO/vInzZvoC+7adb+jZ86TJ39OgR7wce6cbVpAZGyrisp7EkNt5WvksLeOafHf3qCnTb8zoW65YuAJ1lP4bvv/oIrL51w68QB147szwg6rh+i97PdfRR4Pj+rf9LFXiy3jA955FY9qS6RuW1NtE4RImNzBEx4JucQKNWtUkL0Xcs50BohsnPPctzyRhLzsW7gpGjbmPFCcnWc8574ehWMJXuA/G3rAZPQiR8G6PzCwx5e8rlFc3bVo69ZFykUlxpOOc8DETXdeVcXAnroQMvJ8guEZh2J/lQtcp9NXD3IRGY9NzEmMGaj6efZFq4BPUskdTzYDQvgxb6EL7/B1uTQtDyHHG/S6VLMXV8I+eIzbGXpoW7Yp4hU31SwU9RtU0l1Dvdjn8F55/Nxp05M0HNSXKnc4yOhskX7HLtTmzfw2vVP7XL4ef/pDG4+bK8bdZJyn7Je0flvUbqCU/V70sOgPGnbzrbBn+XTE+y00XflG+MpnmLQQKmO+9j9ictA34kDbn5rrx+j93NF6aPAtwR1XBTRqINq47/+WVBHOATqk7vXk2q7uKgKm0gsk59tMnD+D5r2zGRgm1JNSjG9Npm+25XhDsq3LhCJJMzxp0seIgqRjR+ODxdOdFp63WuJ/N3VQ/edoTofTPXueTeOyPKELw8njCEeqZN8O6Rt3Vprh9LatAYIzW58IZtYPXB+LeATdPyCol+jfSdzc3CkpGeJpE5HnSua9iz//2TatJsWKvyeQY6XKeatjjnyoXZ2h0vacEK2OhuqOM7j4so8PcQUxUzdRiq+668o2VEfdR6NII75iHc8kW5YvK5i5bKlDQ/fscuj1j9NJ70TrBumJtgHfEzMyzJlPVdH3OAZaENtpU9m4F5r1wbS6QmdpKkLfJZXTHO+mCrivJQfXDva14/Q+3EFn0SBp5WOFsV9kvFJF6KOcIWncFLC/fukJPJzhwwcIAg72g7Rd+1HBz2nhkAWuKyy8dHLny+XLaP/u0z+9j/vuSvofJBOPMHxLaYNvwWwPIjQfNMmfQF96cIWtZ6grr0UaVnPTGs24wgmQiSf6L9BadEPw3NI4pzOvlwmGvXFpw/3mVvXofTZeoBrQ+T7UHhYmSWz9ugaPsa9HY2x3w3Faz9H3wU/7z13zw0VZmtpfvkRnUrvXJvGDFFLz9wSuWMDRSwfdhqFlI/l/CDLwn7dy16dsr3/NucvV8P4XMUrEKPu2V5hHfXlvr+S6sv4ee40BZ2PNM3V5O/nkeynK8mTbFLMIoisOamfrkK/fspx5IR6XOOEzy6LIkjXL4LM17fM55KgXM9gQmfFJercr8fk+7YqKVwGWuQ3jzl/TFWvtx7TwHNsglsIiuOr8fGYDZ7/VnMuYbtewWq9ednl+er9JkKsz0coigOcPWcG3pPAb6ySuifpr2c/lQauDTTWsMmnku0lzEsDLw18NQ186kqKVu/cAm8qyCcfe/7V9PgNR3w/EPIuZdRHWKSTdsI+GkG22LVQ4rsC+6QPq9VcPFH+yYGin1GFD4J8u4suPlfC3g6mfSw9g8rUx4J+t7c+dyVFNAH/hKzRiJmYvz0Bbd55fRmugQeAkIMDb0pFxY9hnZdwPp9gv0bUSgRRtoVvx6I17JYL2J8agE8OFB1su4988EGQ7+eF3T4BTPug/r8azPhBefE1qqQMLDJOYTZLIU7X1JIVQaT45h0gRC2fBESUwqIlkmZ/RgP5ek7Q1Mkkhtk650JMLXEeJRmkMcJHE1jsGKraB2P+meG39Bw/u1JQRi2j79MH1sXnfFDG0H0RQOmL1NyrYDPPII4nBIWcLveql1HBbjlt9bFS9wk8msJ6u4IUIZVxTKRhvfbGm5amhOl4DFM9+X3ZQzIawyK/ADwAhDSi3/ii92uVWjj1vMbDmI2lQjgMe00IfjtdrGCexAxELVcB8KXgR0IceHso5FTML00JsziF7emf74Db4uZMTJsC6s7DvUuUcazyLSWlPkA6jmGLFaOQV1He0XhM+uN4JpAp8LDXTwI+L6mP82AK0yyFGNOSTrmyphcEH6biZQfTJFaQau5p454t/JNkQx3YYOp/2EyNTw8GIlsJ8UFl6WdBn/3yxt/M6oFpQdDDmyHCnBhdvscIaMbtAmZ0SojX0kH/6yPl0TBotQiY1bBLBHeeDmqPk0qEgUUqSdvre0CIOpkCELGWw7IrKeZ7jWC5L+GYM1F9sjwQViSmfVFj2BxK2Kl9C+tTY3ZwRwkDTItfcCu9B7/VIno+ZfilDGVcjCMYZWs4nU+wmeIekjEcmgAU1hOvvuUHNZ4hnyH8dQxIKT/sEZiKe51ygxJCyO46P8BW6WNzuoKcFiShJ7SpdXc68Tlg4zlcICBzAAipZQ9/8q50jZTpPsu/kX27P1hXvMMfwcjlqYS52vdEm08LGXwp+pEVsvuV34ngFuS0zR8cgrlWvX0kt3SAogG4LS/rjmF3PEOpNqUT680VTl1rwsPuwjfOWyRypHDSINLJDPLj0cofV+JZ7nZ7yIsC1hnvtcm2p4CfSD4vCIWVjdoIOyI7HdSeNEbziD4Mj4F8tZ3S+Rzmyxy+n48gIgjxPRBhlRYBKmvArh596rTq8ubor6OgC6atB+TlxyHCunzPVnsoizUxA3UlJetftufj5dGtNBx5VMUDxo2oNWvgqgDVPoNIbbjt7va2d2DzjvNlcYG6qqCuDhRBqFCRgIi//uW/oeEdX1htJaUKtNke6qaCqq5hT5imOVSqJ9VCZXlt/nhx6O1ID0FmJbOw46dQVjXtH7kckJkVwfr0AyAyqg9l5F3x/fsBAKUUudq82AM1fv896Tvbnc2bXKhN4aL0Md2rlXAWzFJOC3ZlKliogh4ruD0VdrLMTBnxAyGNUMEvDaxws99073mqJnAnbpCU/rhAsLAw9Z4qaj8hQTPKAn4kRaQ2qLZwWxlyKuWXDgbHAopCAMLKthrDclvApa7hcjrdOIONG3vxCkcRWtSV7pX68pdJcp0rqjzbQvYTyedNSL0vfTvlZKf18XeiD/+RKjbLtqqSR9vKsl0dOG9bXoX03BNY3xCgsiF96rRqQosOqv9pgWlVY29IXn4E+OyW7wZmHIq3L7C6I4Bj7yiPpDSEyhOqpFoMErZ8dIa2jKxE1BORutVmdqcrwoMPhKjTKwIRj1zo+8IysqhM5D4TTRZQGwduobK7LAJME7/fwnND8Fstp/sZgl9KUEbpvgRXdOM01wp9Mj+0aaPf1ES8qYgMy2sE+YWPXJhr8qTRD2ZwJIdb1Ab1XQ+jNDQHiL3AnRFBktklHOALGhxrXg5+qbnH5qukFPki3SDDwP/HPmhXklxIY2/D+I161VyH/MgfDd3tVj5d6oEumFDd3ecs+oJlA80N1AWZCLe9nmChz71CO02mkJ+FprmSvVzFEI2WUKlewPp0hZt59XoknhrmJb3AP+Qnkm9L6iPdG8oMOipje2Y/+znREnw+/Iv/iI3g+0G+rv7ta1HPkuACVDakz155I4atmX8F4GnlSI3w6cHNy7avYdBD0kfP+GDGoXid4sYk4wnlkZSGUHlielJ6WoALKl6sYCvBbp1xRMNAiPZjGyEAACAASURBVDqBLITVOtJAxL/5V1Rw7i5XRa5toMx3tPfCFC5whmkUQbLmuSaUtT4fYJ8f4aoLAMNGaQCH23AYyc0gIcisltP9RB34wbo/CFDGL8L934lwRTfO9ppb/j1Q4+bf0zk2be8RgFpI0Yx6UhoMSuFo/dyABOMwxpw23mElNgI8gysEzQwBIVv5w9/KJVaa4/a4AfV4XfB5RaE5qV78V+ae8XAfNrR84MuAHwVE7eYDPz+uX0m1vZlOT4rswflAF3g+UG91OsDhVMO1ucBhv+ZziwI9SxL/sqNzsrJsQqMhWOmE82rNvdkoBXte8H6fl0o13eiNwRy9qfxx9btfiz78R2ooW2XFQJBv105tIR7Ss2h2ASr729+wb4rllV0hy4GrMgqnKw6iHnBUxM7LYgGvGvo+PyJb+mDGoXhFud9eHklp6OVnC4wbaRDjMj9BUx+tg7DYyDiu3QORNneAEHWCJSDiFzmstpICwN5RFCWwP9XQVCW3/nCYUgFGieXWXA1Udlk2vRY1GUyA32ox3U8ZfilBGf+BIIqj6ZYWOFQlH762/M983wugdCM11y2osbg0UJ925LTx+vewTVEfGeD95lxARkOPa9KH7di6pYaFt5wWgANVGBMo6hrwKIYomsJZ2cwrcwDsCtcLbOZza4LcJKj7Rc9rRThefYKqukCxUav70k14dZ/qbTFgs4a9mnvDdHKDyAe+DPhRV7LOVbfw81dS2DNi//LkF9VqpR6rBRQNwW1FOG5HMvdCDaFaDTo8bRnnbHGO9NJc4VJgLyWCZHOCfM4LEqbbEi7nExyPRzieLgE/kXw+VElxoZ6uCmiuFWynOJeKc2VX2YeVzJMZwlO7tg35cNdObSXF5chAiLBSqQiVDejTLq9cy3SvLTBt3ch6sP3GNDjaI2Z0ekPpk2HGAf13hbWu3l4e6UpKjyToNGA5JQJm8awUPlkXCyb1Ty2cEEGkOINxUJNw6p3JdGOGC6xUdb5KQEQpLFK+bpk0R5hbwMJonPJR5qqwimN1iiwiWpYFsbQ676ORSxl+2xG0c+HqZwTzHQ9DSVBG6X4IrtiJ0r5w0j1KGdQIdWngoGS3yYzRIw4ktguz9KdFY24yPbxW7clh4lUpQzMDQEjdcwhN9OskXqsDzJLWdlSAzjbmaHj9nO+zLruATXx3QSvAwuBLrx/5IlD39DA3X3aH+/QwBXbkxfzSsYkNFA3AbasCMtOzjQBPWlUnfQckxR41QmK7vVN//qqtOUgr74/mUPXKhNs+LwmlC6UJNqKorBjDWp8XLvnwgyDfrp2s4VYIQXYlyWWorF+fqteoyyspWHXfBtMOzcva1/QZdW16Q+mTYcZivCHZ31geyWkYAJhF6B+CBfkwOXtvkgQwxJTwb8NAiDrlUnjDwkKYYdUjIHLYTV3BbVmGQ2a1xPQpwi8FKKOCkLqihuGKnRg7FxLEke+H5yo6AeGFmJbek3QjLDParQaL1eoP5MZd8r/6kXAaIOBsw6edUm9FxSXpDH8O+dENUW/8LPl39zUbKEpyCgp8yL7dqNTVsPzVeVX0E8nnO2/TBTcUFzSqgH6ipxXsJ+U0cjy+d+71YYwvpGdbHvu77PsP6NMOGEtPh7Ai68F5UbgMpY/T4S8nHomX3+lb5pGwusnplye9zbx1gS2xdjy/G8Dr6qWBT6oBtVhgSO/tk6bgmxTrVZ58k2b90ET1KqlrdYS8OHpbPB8q2Suylwbu0kADZVHAxd9YvCuk18NP1EB9epUnT1TnTzGoXiX1U1TCK80vDbw08NLASwOfUwOvSupz2uUl1UsDLw28NPDSALH7qhziUXefxDM1w+vfcWnzM0P9NsOilVCGq/V104g7+/3IovvlcldZ2iFgPJPFwb718PfTBlFAI9ie+xO6twL9LLr/LHLc0teH/N4cYbXgrRzPie8diP4PEtqfk55wKHa+E/OzWuaOexJt32tXDjpxPJjet+TziCY2R+1uc0ekt19ecG8P7ot4/d3SwGciFNP+hflzKg8ECy9We+++p3IxJjrILd3c/v0Cs1EEM+Y53X7ceYIbU3OvjM6j73r5mXzgXRM6IPDrgRmMT5tmfA+i/4OE9gHJf/Mjdr6T83NL6Nd5APsTIkH+wfS+JZ9HiCsaY0+KPEEgRCONN05gNsuIuj1b/4fu9eYIp3xNFPLJZALJdAllxa3ZKl/CVJGVb2ldCqP3XnOERZYQ4Rsp33EyB731QiKtyxRkmTY9WB5HwHvekwnFgi0AQKIzS2mX6MJEbU5msFpOFW07hbXajHPAjZ7xDOZZwiTqdGF0LFG1UQ3H3RJSpFejH2QL8oPmuIE02zC9/XqGNZL24wkRsbMJ00HwXUlOR739S02lHk8gTqawOSjKav9JkPyAWp1RAot5xrpIMrMZ2aVr10/1PwDZBwZSqlX+nM+nkBD5PoGlOgkAt4kUq1mbV+IENPn/nnS5qnymr/lOE2isPXCjZAWX4xriSQJZmkA8SWGz+6sA6V4gdT+J6M/0/fsI7a7+UPdjpJIninI/W5u9gXI+kMoq/30732FPBtFaM5Wf06mKzxD6mw784GgR5OX0yr6FCDopn8vlhz8dnTkpSkjkJ43jbmDkac3nM1j/6udM01XX/+e/+995F/tiC8djDlPahMikY9c40nV9UDvhb4YRIHNr4rMi6W5od/sYikqmIEu06eHydFN0z3shQrFoi1t05l7aZbowde/RrvECikPeoY1oflu63MFhz9R5Hv6TqfVY6eGGzXi+hWO5Z6pxvIYfFJUcMT37GVLhJ7ApStgvcXguggmyxTR9wkNB7mrYvZLlcZ/Ejc3kx9kKyhOeXYXbLSJYHTGDMhlhlCzgcCzURmn2YbZFBEzX/nv4jogcCWwPRyhz3tSOQGNDyO7ZQI435AODKdWKh4d63ZYnyFesV0RbVblM/h+eLleTSue9dD7iaxJZvVaQgRi2hzP8oOyjCeO//ZVMuveTuv8JtpLd7vK9xwjtrga17vH0ieNho2gLeTAfSGWVdL+28p3Oz9kqh1KdIkH5WaGXXOalIfgHiPQh3xLzuS6jPRR5KR1WJRUgRBuytmqhOtfYlYwskjrogvSOiajhYchkbom0frhcIN/ugficTQPnw9oQs9lZ+rTp4fJ03e+e99xnDaEYArYQ6MxS2vOf/yXN02gMCTIYF6MIRsQ2xIK5hbQ2FlwYx6Rb8jfAXkF7QxRoSo+14x5byMtNAT+YcJmdl+nzJJDWjceaoCwEt21lseXsarh7FZKn+yR21SrRD7iSsnhx1Z4qMBSVmI/Gv5/rf6IP3EOp1tDWXCNimYqBeg2R/4emy9Xjc31NOjUAsXZz4mbiII+2j/Zj7vm20IH2mtPeOzmg+ALHfAf5EXV0hfrCx7sQ4/MO39NyFHoM0uLrcVniOzGhP0fq5q/TGjmWc/gSkEUqq6T7rU6YvmHn5yPCiCM+RUJj1Ozn0S8Z0o1lhJUvrPTKviXn81B+ldLRVlIhQrQRTK1+cK57k2wq09i7/11Hd6/vCUMmcyNRfexdpCFSkAXa9D3y2Gm55z1yBC+hmI9OYIyMxskgCRt37mMXO6MClH8fw2J/ApEyX2IPNVbDuSypppWzU7Y9Xp+T6rTpdGlYpysbEvDxmSjd9vbYmXAVt84mPmNBiZnBxaVgvFpOLYPvMySP73nJD0hGq4JF8Cf2uhDiqzOsDu+Z/if7QICO7S5CcvIjyml0dz3DCoGzCl9Gn+a8uO58oJQunW79+Wxfqw4b4gtqGeMZL5YwfkOVFEKD2xMN7N9QLnMtkbqROHHaQWqjplQv/h7f42fvJ7Rr3elPyivT9igaJv0k8Lv/JOdXEMoq6b7RCR03M4Ioa4/FMWQh4zvd0wO0z4fSK54qEcrngVMvpHS0ldQQ0rg6GVOz2XQlhAmK4nVbOJmEu7lJm6j/OTwMPuxulC7heMZWUQPrmFvjrFCr1lek9e0v/ooyqY8SLNGmh8vTTcs979GzPkJxyBYCnZmdu5/27777i25LyKILkxNbBbPt1CibfYSLvtbDYj4KNKVntDCLD66nLWTZEv7wG338C9vOprcjzLbtSdnyX2E1wSNX2ozc1TRfheRxn9cVms8POO3WAh81GoCgYp12Du+5/kc68/nAPZRqnd+skwCohzoruBcY4ZAZn0dFQ0DK5kPT1dMjNXxsW+FcwhQe87VaODUAV5thT4p7S/Z3lId73i0ZRw9t1WoUondywHYvnkLAYdnpkX2P/cR6diCh3dWhW0mdaWWq7klZ4Vv5VSqrpPssK+uP42srKR5aG9KTwrxryWOlVz5VIpDP1bCtr/yQ0mFVUgFCtEPjtcnaqHxD2t2f4IoEbJoL6rbe8bnmnMN8vgI80dr9GxoGzl0kSHFWizHOOc8l6HkN/I3J2A2UG+5xfPdLVLSfgizRpkPyPCUdtt7yMzQI28RWnmrlStR3PTa/yPHAwwZynBCNMkMsd9O++5NMF7adGO1hX3cLsJYoHaJqa6I+9uyuzRmWOAcwXqghDMwsmrycQlE1cDkwIJbGxgMUZJqElajqASq162OcPr8f6MouWeZE695kOHfGlVZHFwP9D118iP8ZP+v5gNaVh3TvJkyNXETxHI51Y04CwGXFVAkK5P/B6XLjUzp4jq/JZHWuPBI6R8v2TRSHG6Q+0n1L6sbFVM1ZnRzw1z+Ty42Q77lpf5DQ7gajh7Y2ZQXNRZ1ikG3hGpBFKquk+6w/VUlROTGCtYovRTI+nuVmle22jo1vBNIr+5b2XU8+D+RXKR2dSgocwq1LGtc9J03WNtfQmKMSuMs+hpXudVnWYSVEoMeVrZ+owNXHLYTCwHdCNHE/aT1ACRZp03KanpUOHBvfz52DCPU+KckWEKYz4/iyHjaZbkpS8aXghQ/6frLYU6+X0uH2pNQ1trzsnpR9LVGgMT1don4Cu1PTaRFjJTc1JwBHdPQINTBuUNVHOPTm8SlMoCxP18MgQMPWldTY0LonsFFLRu203/Y/m7Q/ghnZIOB/IR8IUMI7KdOVlGX7dMk90BD5/550deJTOn+Wr0mnBiCdn+OIIf9126tiWcKk+4V1YsIk45MDQuWGlEfcdON1VaxoTpvy03hCMi7JV1z/b+nxbjhcSbV5lY4aUlNXoixSWSXct/N3L754ASeMzyL0d5638r+U3pBvhfK5mF+FdHQrKaVJJNlKpHFX2fa1TAxWT1ErwRrPtV9W32+GMeg5P4maCL130qa98jwxHZicW4Riny28cpFu/GmnyeIn0MqV+nnyuRKo84qe3Z8ubt9mYn173X7rU5Cxx4hDf1OzMKB9uv3G6b5Nwb9Fw+b4Q7JjnLL+8axIPm2aV0O2Eob875YPEOm9Dar7TQ33LXD7gDrNwHlgMKk+mK5uoMYH+lnKZ8Pey84Ngax+vUJzla3B1G3f7xXMqNLOAMcc9F84fffI/TZCO/ZCxrQP8coUfy2g+ZRl4TT3h6Ok+yZI/IJ50z2aofOAdCGll+/3fYDDCedzf/nhpsNbSUlivvU+rttfbM0ZnW8N7qu9/62k46sp8N6Ir0dYzm+fV3ZvsO/y/PUE81T1jnH45l0icQJtCmrZhytx551v/LJcz2BCiySSzqKhz5LsYhZBZC2c+CxyfUY5PrSS+owKeMn00sBzNVDD8VDAoTyZBSTPDd8X2hWORQ5HtYHe98RP7V59PkJRHOBcf0gz4W714vLtgpbD3/3qT+6FVyX1kzP5K8EvDbw08NLAj0cDr0rqx2Orl6QvDbw08NLAT04DvUqKVjnpFWbvoI43h18dYDoZwSSdw3qZQbIo3kHK+4K8HLawpiXh9733TT/9dIL1N62t+xP3II36/oj6b7irAvtPfN07r/z4cfo/rlOzbaaNtYblJALc4P+Mv14l9d4UZnvt/iMJqA8rSGcb2K/nEE9iA8t8JKznvNPAAlcRPYkY/hyZvn4oTydYf/0kfS4JHqRRPyMRIiH7GYG/OYxXfnyzCu8IABss0QhJOPaf4jFaNB3713u/UyUlU5hlEncnIpeSvjmCRLrlPUa8wQz3Zd1LM79eDrCcZZAkCSTpDLYW8fpy2ECmCdxIYtcUp+MOUqRuIzE9TmAZ6PVIYZTrDOJsYajgcTqHYwOANGO9/yjdHOl6NI4hSWJIpkj+HqhDUqhAbwaBhu3qXdHp/TRsEEn1HVt6LiQqM+Jx4mRlHBSvJ0isvkGw3p4aURYfEdsjEsFcV9NE0dtjSOc7I4dkwx71O2AbiTTvl4XvElV+ksJsipT3GJJ0DvtDTqv9JnEMmVqhKOkN3VXyM4xBplE/aFv0n3EMG727nq4nsCprCBHyNSGbSN7p2ugd6gOk4xjQvlL+Zx21NPPt6U8g2fGe0wS0Xdz8SBveqUE7IV+ZrXNe0IJpnSSwWMwgoXIhhdX+APslUvAnVLbklyvuGqYTH56dpyQflfyfdC1Q0yWyP+rEdyoB3n9Et1rH9idRJ4RKigG2A/WM+8/KDZ2kweV0DNmCj/eJQhRm3gDmoaLbUuJ3s5lQUdKLP/AeBQ/ptq2kHqGZy5Rlhl5GkCCB+6Qo1qMZXECiLLuJAJDDQMgo88+QCl7sl7TkN16V0Jz2xB1DTNPhXLfPzecwX+bwG7XTe7kv4ajow5Ol/5wmP735DCIN29W7Rad3adj30Nk7mgkQolsUDb+hryu4QbD+tUS8H24riZg8yIa3bKMBybsDnI+K5p5sO2rxXegNwVGyhKJoeXTT9R72irdIxHVFp9atz1Zvsp9BgEb9sG3V/iqzSVrjlQrkuDHJxUfI14RsjZnSvODzFunrSOmQyfQm3GQK89kS9v9XQmzJ3fEM5Q7JMLxp+9E0+fOjpwwzeSeGTVHAKhtzYzNdQq7I9ojrssu2Z+Up2Udl/9flT5+aLhP2xVMJBp844fPy7r3blRQTb5AfGtRz4ISCiNAWhvAMMIjE3ZXTGHKqDpwLkW7tSkqiErMRR7DXUGc8m2SxghDRm43oIxD/AHOkCMQz2CO/rL7A6XTxLg+Ww7gaeKpOOgM8cVc/k7x5Y55LzA7QzHVA5lOgN3//PR15ke3aLYlcQE/hojKa1rvOUC0br6Vhu3YeSqrn4Vk/nby1JSfCvg4RrGVZvtxpqz69PmjDhU3rD9hGIM0bUwlfuAAeG6IKDYUYLt8FpqYA1izDvt7onbStELWf6bB99G1Zn7oaFAS2KiV6wrrm+Fq724R8jI9pJFwZxSvc+9jQPAQW7OH8z1RtTZ1he/Xt+HCaOvkxYGOTd7iQ4WmOllFn5t3Uc8/MU7KPymUV+YXVUNLU9DpA9icdWkQZfSrB9zhEZ5X5Q8sCnxeFKinibg7VcyAdVElRi0FJYJwxREV3pTXOzZlCt7D0MJj+xIm0TkEmUon9NHPmdXWZgJr2rM9L0XHpT0Q3SZRlNxmhMNqMyW8ZJ1Y9NU0X6Dx3jw4lerNia9nkcNbDCPILk7Ln+kgUxw4oqdGPKVhUqpXztGgrVxt8HdK5bUt82r7uf28J1q3u+rIMtZVETB5sw6Bt/KR5v4bau5xmKZ3cYHDP7XH11vEfoldzhcB2sGgtFs4mpM9WOs834y+qNWj5BKflNiG/xCMfRkuoVO9zfbrC7fzf6ki044P+CnZ+DNnYpJ3LLNMIUPW6sYPzHGrxrXkq5KOS/1MlZW3+1dT045UPQUVsmC7z8HNRVKZh7e4Ue9hfPC50WE7EOal0e6IODB8FckPP6jBXXzq4J2Vae8gb1IeJ8ZkgyZoJEZjQ+nyAfX7s76I3hmRnZ4NH4CPdtoXX/TTpEGUZnQon8FACoqhcL5Dv9nCsfhApy67O5TCuDgnbAq6aTMFDeMa5KfA7dCjRmzf/noYT25ac6u1GM+pJsQO0hQxde2jYlLYHSPXck2pbmIhX0nRy/s1HolYVlkCwlmX5MthWEjF5uA0DthFI81gghP7It62Wa9cX+NwkqqTozCC/3rrvtH7G+cayg0WjlvWpSlxJaNUAQhAt/Vn52E1Lm29bmeidyw5G0QgyPA5kNKf8dzP/WzoK2vEBf20rKcyPARtbacV03KyknpinZB+Vyyq3ktLU9Is6+sJH9tfxaICSPpXgb/5y/OZTK9hhdMM0hoOdN9QxN9QAHqhn3bDxpSOSKcwBKrqWUH9aJF26FSDdGmd/gCYdInpXuRrP3pbQXGvY4/HnUQT7SqYsa/H1pxyGkzGxNWVaehUdIhilKzjV/cpMoplrx9FxY+HPzzL1uj4pevP697BNsZXkoWH39K7Gfz00bGNnD6k+RHVHSjKeqzSebaG6NnBU8wY4xMitex+JWh+l4CdYy7IMt5VETL7HhpJtRNI8Fnv7FSx3p9Zs1jfj2+pe6yN4o62kQnrrvmP5WYBGLeszfPKAPlGAbNtUsJtxnsHCxU2Lfd2VsYGVgrnqBm2IlG+Hg1qR7PhwmqCbHyUbN07e0ZWUHoY0aVS9Sx9h/lEZZR+V/V8Pi7rUdD5Q1E/216cSLAs8rPYCS7TTeAF/3POJ1EtPWXDFkypm/pMqLFc3X6/nLc3P44nWxekM52MBczoBeQyE2hyoZ/YLfzoiLBzvJ3EbGfmLNfSgf5FItySMakmFqMTY7WUCMhbQmiYNIBKCewTulkAsUZa1rO2nTDF2u8j2db7AyV8++8i+T+GKNPM2VvPNeXaUMr0ZJBq2q3edoayuv6Zh45yBRJlnB5Ho9CGdyyTqMMFalmWwrQRiMvpzl8Te+sFw28ikeQxDYq7Zvo027cbXDvcByHrrvtMNQ6JRv8W2uFLPDBPFKTVIkOjtpsW+dmW87DCMcTuHHCDT2+GQ34t2lH2Ewohkf7Xz49CTHdxhbZPGd8lTso9K/s+VlDWkN5kzxTxA9qe8sMLFLOq9cUqnEgT9hXr5/oNjTTnlfDntFlZZjXGN2xXUThkl6jmQDrNP6haF+TFyLpJ8/aRbnc4glVigSaPya4norQjc/Z6KQFnWgtifYhj2Q93v16bpD4NajyDZd6gOmQJs9585IJcObAWvHuA5KpmGLdC7B1DdQzqX5MVx1xDBWrb9cFuJOrnDhhiGzzY++c67KYytuYGeDe64IeotGIZEo36Dba8NVNWNocGgTNKPt/O/flOyo88G3Lu35ud0INanmx8lG1uv+L+q4ap3yVOij/b9H3t2IWo66U9AkR9X3ENe0dkcbTK9um1/vvMb0twrqGo8Ne7xP186TCX1eLDv9ObXoEm/U1I+LNgHadgvqvtwC+XLOezPb8mGw+N6xpPfom0/NE2fJE89Sk1vyjXEE66kzNzjMxzrA8P4vJUUfA2a9Adq/l2ietGw30Wtr0B/whr4HHnqYWp6fYZDUUB5UourfoSW/MSV1I9Qmy+RXxp4aeClgZcGnqqBVyX1VHW+Antp4KWBlwZ+HBqgebsfwch1r5KipZjvSEGXzddAsV4b3p783PBfzAqd4a98uicH2UMRsXFV1qf6q3KIRymUD2eE5/oE7+uagN77LOrqKxLGRZmEH4b4eI8KXhW09w4RRmV/hZEQU/92b6Ve/5Hn3XkPqr5l5w9Ny/O08mBINWw0BkrtbXswoA95rVdJvTcFXUzVtaCl5sXDBVo/5M9Na+7L67vDBasC8voewHtmBdIbShwp7Dfcr4up2WD9UDDP9okL7j1DttyNv69IGL8hWe/n2z7uUsEbWCcjGGcLWGRjGKWbh1dj4Z6axYohoD3BnnzjXaj6lp0/Mi1PVs39wV0PtGQ825bvtKrzfpFCb1AlJVHQe9RoiVo+lCgskm5rWCUjXs8/SuFwuUFnntgU5Qa0/BOkGq+XkMZTaiFqWjMqQCLs9pRzPcNqltKKmDibwWKaQLYumYYsEKMxDIlq7IaPmWGWJhx+nMGaNtrhXs8jLInqPYE4yWCj6O68J0RXUgJRXe3lGCWZoggnsNgxKaRPnf4zFKuZIsIzFX6lZXCElejnuDFQIlfbQSDte4w9Kao7JdmRkpzCeruCdMKk+myZ4yaDvk/ECcxmGeluFiDtS/JV+RKmKz/cVyaMIyJpoL4E28p6tLXF371+1JQwHY9hin6If5c9JKMxLPIL2D7uI7f3qeA15FZ6pqs9U8wpD/vswFH6aNq4yi7NkPSPDSX5RAMOof3fm0YKYg1xMoPVcqro9imsDxXgCjW9Z3KElP0jrljrlgFSmG2s/E2ys05Ldd5BPE54Iyq90sB2OoF0hboP+LDjmz5bYHCyLwzLUyEaulSGdMqA//5/gv/hv9H7rcZEvJdk6rw3SWHzi38L8QDKP6ZTsodbp1wGnFAxgIIeQUrU6L+H72gncQLbwxFKRQoeLw4GMPsW0u05R7L4CBa7A9R/5v0+QTqzoigXv2Jac7baQ1msaTNiFE0I8qlpzRAg7LLrtv/nM6wsY9iWR8jVRjhGzssyyVTjNlz+pujQ4ynkxxI2UyQv48a5EDW6hZHyhj4/0TmmDXtj2BxK2KnNxetT09Kstb5+gdirCGabAk7HAhZoU1+XP0A/lwjkbmrt65DsSLRAm63zA2yV7JvTFVyf0M/N5zNYB0j798t3IogvEr8PuGNeERSI+5gP1Jcmf7u2rWRyv60f/B7yo3KFG8ZHsDudCOQajeeAHAHj4wK5/X4qeN8OIk1bIdQqCJ1o0E1lKI1MfUAY9AKKQw6zCRMS6htU/d//45p8un8CQjfuIEnepOUMWRRBrHBwGr6KQ+lDfJh88+/+ligMc5ei/4Q8xTJE0KOha//znjyhiPZUBvxr+Nn/syRfWu4KOF1+z76v/HY7j0mXq7Jfdvz21zqcMOU/ZGMtP9cpP4P/YxzBKFvD6XyCzRTL3jEYApUyX4CC7hK9ryBRyzV9W0NQRaJwgHQL1AVVbDKH96SHsxjX4lCUkQAwWZshi5oKFd4xbdAmoXg7fsysr0yfPaA5dQrZ7+XkIciRjuPwEdi7Y5dsvD7dcw7S8wAAIABJREFU/de//DfkGIgvoc3P1YEcB4/0aHtSt4nOLd+voqNSsAHh4l5wKet2V5K+mrqCAk/WtFhqWh08zNhSsLEVuRhFgDBiTm+fXK3f7X/ell37DvoBVkbUQHF8Au9r4nuItH2vfFpHPsL4UH1Jtg2R+3EzZV2rf831hh9VsMBCW1Xo6sCBFs8lktttSv9jdsB8ZPuIpmkzkgd7+YGywXGGUF5hO7Q+Z2DX2Ic5zGnoGDvl2l4aYRQK045ev+ezc5vPABiayqMXzMhD0O4Q3WGzAYdt9lRJpYsNlOcKqvMJTpcanpGncA4y8tDQL+r4DX8Z0i0z7bI2JJPWl9aze02yGO5rS/kP2YOo6YbAzqiwWydUyBT0Dp+Odd8I1PK2EuGJe50YPUFtKosA6ZbDUMcceCopLKBaplhLUd4kXHCyhK0DY9yD4tUv4med07ACxqP/UKl0LEFAphDVWIeDnzj8xT0n+y6OlOB9XQC1nx1q/B1EZwwdmWUoN2e+Vl+Aw5kIA7Xj8yyUcfElGKamP0vk6m6qrKt7ZLf1TN9dn2AfC+nsXvk4rRbBwEa5DNaXYNsSW60+cv/f8bEkxg5z+OWCW7Ed2yi/R202hKzBlufOKLf1cYnczmcU0WjAg3agwijdmoagjtwu2MWyQT+sPkN5hcPzk9ftuFyfDoVpRx+ysx0+nLeUP/ZVRTBlGi26R3fgt8Uz8hTZwiKeaBr6735/qwyxygArX4VkcvXsXqMsfGQLarnFfoXs0forW0aivtt2C1DQu4U8dpWxG4yH+x3PWIg3sI5VBWEXLFZLx62kdMHiI93qSopaOQpKaHZIW+GToqyWPyY6smjJ3DLo9qSC8draUGnMdDMVgOCudJRJQCaSwUtg7/ak2CEskjXN7Uzhu7/5V5QpwtT4AURn009uYDGOAAsmV1/UksHhTDxb66qo95Y+tTqMHs1ajJZ+LpGr9bv9zwGy64aBZeuOT9j3jY/5Sfv3yseZz7KLRRgfqi/Rtt/9BTdMvHos4VCWUJYH2mwZ9qMLzMe6ATOCNR4LbTckRXK7rqTuo4K3Dc+KGnt4woBOgqZp/+E3eig6UDY4zhBKo+urbBfu0di/2d+1DvwnIHTzH4fnt7MdlyGppxlNQWyJMHKHDwu2+O33qC8rfj1SM8thqM+6lZSmoX9Rh1SKZYidxykvceMvlM9dPbvXaEu7ksJz+3AEJGRj951jUcC5uUJ9OcJuxRxJc/SQ8p0gBb0TYIha/gTSre7FLPYl1A3TgIfRmbGlynMs5+MOEjUcgl1ULT87oJ+w6+QhQyI/XBq4HHjCdoLDfSr9PplkqrETug5jykTxcsNHz+++lHy6b7aGS3OFS8FpSjYna7gvQKVXpPIIoZPNFU6KVL6kcWVdkLAs5EDRlOCUOGGa4YGQUQq9YygC9HOJXO2ktnM5lEaNXDYzrKp6tuQTP1j3MeQAaf9u+QKE8cH6kmz7J5ki31EQjhKJJH8cgsJeFi6frwFHD6KIexzaxxtVSC1yPByzgZyGoDMapsJhWk3pf8QOmqa9QGp2c4Ylxj9ewBfq2c2hDpUNTiJDaexWFPoYCFVJUVx+qn4ozE70ATtzYc1x4TvnLedNTKfe2DFUd6ItnpCn9FC2S0O/BvKDq1fd+KNhvIBM7nvutfY91nFL+Q/Zo/uOTH23aexBCnq3OwcgUsvt4REqP7pDHG04Z1ioSWmsWMYJU5fjJa6cOfNEKVY4eUWrlsywR4DOjAo6bnlyGyeW4xgn36a0zHhYvB03plVKczP2H1GBSZUUxiMQo0PkbSd0QDq8XqmE6ZtueMXWEGr8LaJzHKsjsKMI0mVBwzPkWFYrqi5tunwEyRQpySPg1mJXWpE4L5Kru+93rhzCezROIb9cARe1YMPCDLGqa+5FWz7x93n3OSzUD3qhDPcwJtMNnWcED8gnEcbv0ZdkW1GPHQXhhZ+OjUR59JVsoxbPV3uat4tXpUVal8ntj1DBtV3YDq5cCdG0bd8Sy4aBacTH7PDc6zBV35WvJd+70Yt2pjmvtpLSR9RkeHCf/hvqwyDbQvSFgT7LlZTuUUdADVPVYZTyg6vXTiWFK/GKVadMShZ7f9nh6KgtX1FB7XCf5Mf4VPcdPPpmQfN3uqyPZzvqsZseXg1g9kkxEVd36LVV+p/PIOf6SLc6psYm+Q6gM2PFkaiEYRi8sstyNh0wVp44SW2Hb/3mfsVn0falnpPSD4RkEqnG+mX9yXTovijDqNEom4/ajaHjYojbaWTKcj9+LZ/9KRPnSZ/1bZ+xQwvJbj9nf+/4hP0DfZd1dr98EmH8Xn1V0NetrMdekgb7Ue9NkPLnU6jgSq7uIForgxR3+4T17ZE03qDqw+AwJTtb8gW+DvVhWR+yL9zyWeyJhGjofFrBkDLATaAsk/vk4Os77SEVJaaSGhzxJ3tQtzKjcQIp9aIiSPV+kifIWkwj8fygJwT/CuKlgZcGXhoYrIFHaeiDI/iED/7oKynUaXMuYbtewWq9geLYrsx7hr4fpg8/I/JXGC8NvDTw0oClgZ9iefRNVFKWDV9fXxp4aeClgZcGviENOJXUFZqm8Yynf0MpfiXlpYGXBl4aeGngR6MBVUlVsFuoJZdqc+EkXTyVSP6j0cg7C4qrcyaIkvroP0V8Xn02UvpQPbyVgu3uc7Pipc3n1lJj6yf5q0XQlh963i/P8Bs7nWaVlUrHswn6j8hry/ew5gJ2fjhM34tPiMem0xt7+OL6hu49ks4I91RsUl7SOF3ncLqcicvHLLgU1J7Bb0hNXzcpvdWCHyWOsxn2o6J9Vjxvp2DXsFsuYH/qr0Z8iPxvEbSflcZQOM/wG3svkKGnK79YmI3gISmG//aIvA/ZoSeSbOfeo2+68dZ4unR6Y483yfT5X34knZHeeNZrYTe8f4XhqjKVHNUiEW9vqUwiBUs031vhhWQp1xnE2QLmWQKTOIY4nVMFTFThdG027EF9gHQcwxYLM4FM7tKB8VlRB9czrJGqHk8gTqeQTZgEgbIOJrM7Cef4U5hmSGvHtEytwlciNdubYWWyN3LZUpQVdRQnsKTNoY4A3ssKdsspEconkxhmNl07TmA+n0JClPMElorQjsGc8jWR2yeTCSTTJZQVL3C2acn/8//yL+G/VT18omCXK4iTlbEZ4qYm6lqyM27+ncUp2xX3a2zmkFAaU14VqntSAZq3RNDGdEj2f1if7+A3tF8m4u0Zhp4eIOiH0mXbJ5luoH5QXtEOEnHc63vWTcvOOp/Mppj/YkjSOewPOczTmMqAbK721RHGSCDd63Sh76YzmGcxZEhEd+Px0NtJKsGfUH96b1C6ORqafag8erS8uGXHSZxBlmB+jyFbbOGQr628au0Ts9Tc/1rBZp5ROYf5f7pkur7rJ/+wmRqav5Qet3yNGKbY7qq2I8c1+bTjWrW2fFTyEPHWDqv3XaA24zELMyyQPDTfXhjOjZAsehNcutxBsUfiegS4GVIjkzRT9rzFza145pAsB7MJI4gUWTxEYd4TVX0Cm6KE/RLDjoAJFiUT27MVlKcT7NeMBFkN6Lrq+EfJEsrTQW2QZgIBp9NPStckh0okezNC5xaV2FE7XeYzJrqv9gc4KP2O57lFyJ/AtjwZsjxifWoFxUwWWzgec5gS9sdOhybw/wx+SbpDnNMZflDEak0CqA3BGqHIzCV07awxP+jDVcE05w45nyqpEM1bJqXLfve4Pt/Hb1r6iKGnN/oAxD5BX06XpWc6ISGHnz/g57IddPgeP/Y5n33PKqt0PomSMLVbzg8A2g7rooR8xRWLeyqCiadHb5f9yaXTa3uI5dEdJznY6sDvQ+yYrfeQqzKITrPIc1imDEZQ2Fw32M51jnVFNIYl5n9FvMl25zY/Kj/5fj6CaJbTJn461cBT/hl9qvKV2X0jfyVFGR6PcXCHiqxrLhRuE8A7KcILgRQcolv3wnBuhGTBsdAo3Zo3GJaaYxuYKsV4hecvNXQMArL6QnKwEhX4FFvlIgX9n2CKpABdA2L4iKYnzFIF+XYPZxx9aho4H9aM99cMOyNp/4uO39CcVYW/Pv1XgpaOZ3uomwqquoY9ptuxoUz2HkYl7kmkjiBAp9R/vKl6ChfVUm8J7bwzHXXAjaClYcLpYxGQ3dWlJbsU7LawxfjsHoJoZ8tn3Xgvu0xRvmWad0/nVniy/X9giGw8gz2yEusLnE6XNr1aWb1P5sQ9329avaEONDiZqPO53rrREvTldCGxHRuw2naPySvbIUAc7+nKuWHZRdtMU7zJNzzUbjE/KL82hH4AQlJR/u3F46O3y/5EZQ3xNXl+2thDKI9g8EkOjj6C5dOVCBAtVZ0xRfqkAX2ahdZfP2R9h/P0hMpQvnfYLGFTXBw/aVF1ofS4douOazynZkZn0+go9SedrYQtTMsg9JsqeBBlEyLe6nD8nwIpOEAE94fT3g3J0joBP29P4JWrGKLREipT2F9ND0t3yfVnSyZvqcJivH/3t4QbsZ0cM7eGMuJwJ/bodNj4uRhUSeGxBRZVQ1cEP/tbdZ5WN8xo4tgwQPYeQiVuNa6+qUlkO50MXB1BftHDjLrf09LUbRtQSJZfufayKyL7O75nX7vvmTgsH6ZnsKGg/jpHQgikf06Pn5Qu2h97bYeNOqqdbRLPtmaYUsff+1TMQlufT/MbNdxn9GT00tpHE/RD6TLvo/APyivaIUQc7ynLuWHSUym/sPKprpjpFQvjI+UHla62gWURaHrx+OntMh1eg3/ZD219+sojFPnR8mKwHTtoI8xXfMSHBoU7mm4vFbtxfmh9SP9opwvv2ddSejg/t3aLOPNFMFPkbxwPTLELVu4MH0xDP31Ucox0CIFYC20+JVLwb3goxkfzNe8KX0Ky2MrB1zvXlx3RjjM8wkIdAMgG8lO2SYlWJSHH+1+IHG87uT5aRHfrvUR4IX36NhsxBj57F3tiXBGsjn+knluiDmzD2Z36fIB9foSrlamoFewlodcwhEqs5TCfaoWYnU7qnWDjR8drJuZVb3KmelIWwV6nA3tSHfvoikjpnBcAzJjTh79Zw3/ue+Zay6EpzaZFbb8v07xZ5xbB2iKly/b/4TF9Khq/rc/n+Q03bnp6seyjCfpyuq6OfVhv98pL4XvtwD0zrx8bpxO+WHb25VPdQETWnKZ2y/mBD0Ccml6mdSpCIB72FdSz7E+GtD53e1I4uNMvj95SXgy3Y6sT1O7gSkqdtZVurZGU7Rzm26PjJ225G0qPa7fO6r7Z9gCng30uSQyEP9WE59kWqqaC3YzH/bEnFSLeCm5Et/WCjR61OUDzDYWHv4VkMZlSBdK9bmClwLc6Y4Qo260TcmByvFc66gPnuIqqpaqbIzSiYWR2N926Ak1XBTTXCrZ0wi/Oo4VJ6XpOipzWS0KXqcSuDN1rnc4MiksDzVnR1eM1NKp3FMVzONaNIbRjg+ey53m4JdK1rxd1UjGfvdS1D1YkOFTFFGzdsEIqd3M5UENA06rd98y16u2hz5p48zM0dQkznAvDEYMQzTtA0Jbt/1Z9PttvPMN9AYK+nK62sGE/0Pa/T17RDiE/7jpe/8qys5tPjS/QW22BjPcJSo28Y+dkAH1S9648wWGL+lNzyoF4TLwhf4KKDhHVdPqubP3yiMN8rLwYbsdWJ6giXUndHu67mtMjMP/Xpx2NIOHpxt10tX4TSo/Rn7Ku2Se1meGwXztMNIm5IsLzo3Di7BkE8K5HyaRgiebbfd93JdOQzbCPes29vuywwBzDXg/NByjbpESrJxWi/mJlN/VS1UNEeF/a2nvaeSZ0zAbabAxrvf9JIjWrQhYL6RDZW6ISt7EL37Cwt9KJC19Kmm/joyps30qXOBeIfw3s1XHx/PsYVmq407WPTcE+NBWsaFKX/XWsKxkPZdmE06GtX2Gvjsk2cqnVfSGat0TQDtn/YX2+i9+0w8SuXnwE/VC6zPvKko/5uWwHkfiv45M+LTu7+bQrczvcF8oPABWs9SGhoxhSvTo3EI8db8ifbDp9VzbsTLnl0ePlxXA7tjqh3KkO7DSdbEnn9PAR5tYJF6N0RfWGm672Wk6PrT8MukucuDZ8nLVCODfnHBbLXTuG/hQCeDelYVLwIzRfLPtqqKp6wAR1Vxb/lUzZ7j0fiJfp5L037iKz67fZiLzYpa6Y1q5/05+3Sc0hsjf/JlGJdRy+zx7FWQ2LLA4V2cUXpuwDTgwOBZvjkpjczrueS47Xs28K7ago+P3XAgRt0f5v0SfmAY8UdxD9+2/774gEfTFd/XAe8XPJDhj6bT/uy/DYHV9+aGCTJYBHsvNfzQurcHXaHX8h/3bp9LeCJZ/vI/Zvvca/32HHYQH2n7o3Tw5JT7eS6sf5uvMJNVAX2Mpq52Q+oYitSE1Bi0Pscf32x9e3lwY+twYKtaVhgmff0cjFGHa0JPdzy/0tSfeqpH6M1qxPkBdHOu/q84t/hWORw1Ft0v388r4kfGnA1sAVTsUO1qsVrDd7ONWP99ztUF/fh2vgQyspPLzuZeLhxnn4SWdY7OFwXi++NPDSwEsDX1kDYiXlTl7dK2fn/bqAVC3K+O/+t/+1u8fn3oDt5z8Y8mlH/czv7WTiY6Ha719yXsKPR8KvZu2erMdC/qRvqZVVZksE8Sdxd/ywfWZiqnrhik+++YdO/hBCs+3aeeQD/N7G9vDikhFM0jkUF9XMfC9dWSDhITrq6OUrXuBChzHBAmpYqsNXzaKc0Riyxc5smfhoMW2Q7TPifqZdcMP4LeC2WEldcdHEav/w4gP7/etBLR8+XaD6p7eF21HyB0M+O3E/8eIR6KIdvf0+7qeJ0g2cqwr++PMVrPZD2Vt2iJ/9exfuedpOIRqlsFrhXF0CNzcfisnrhis+9oQf7PwhBWfbtfPMB/g90yYS2OY55Ps97DZLtSk5Bt6z+T66skHCQ3TU0ctXvMhnE5gScYU36eKWi32Rw36/g7U+YSLdfIWRpC7I9hkqeqZdhoCII8QCraYJIBQQAYPpnFfzNccNpNmGV/YFIIvZJIX1dgUpwUNjyJY5GUK/fylXtGYeW/bjSQa//p0VLvihhLj8dJElCnIaQ5zMzbEhIcinBCu9F/IpwUJ9BnZhiCHYrCSHgX3i3oTjDqZJDJPJBLL5kr4j/JfiESCW+v1y1W4jQLLB7yyYIzrWLE0IABvHGazViqWhkEcC7voU4IXwXmE3i2Gc8PYF3LiIy3gn0y38cFxDPLkXjltCFicwm2Uk/2z9Hzqw2EuxIUgtQUSzBZRqG4EIm0WemU8fFjQUl+0WKz90VLJjXz01rNMJzHZtQ+GSzwmGe1H5qzrvIB4n0O4XbWA7nUC6Kg10FMM1foGg1KTdp/gcOfuS0wbX0cJppPIm28ny0AGsSmUIhnrcLSFV/pyQba6AQGAfIPhSrlVZEQGBhK0yCHt2w0CoAuhYERswX6GfxMkMitA8aaAM6msLAPNeTEfwKJKEcxxPc9pwT/+g8vIkgYzyI0KP/yz62uB0C/LaPWIE2ZarFNJVe1QQXzMwt5PHNsfW53plkVWGC/H6dET3dF3iAW7jHjUs98lGSQabgjcHR8xYi2F3PEOpwIAI4dS7+DG/hyCLBAmMJrDOD7BVe142p2v7fnNRYNUUdsURvlgwUD+U8J9gi72BKIHt4UjHhmAcYzK6DPmUYaX3QT5DMEaf4vXG2tuwWVkODZcExQqL4gUcjgdYJDyERXubCFESAf5WHHLek6T39ihoIyJYUFejbAlFeQIDc9Sw3PEU8mOpNs2OoahkyK2bLj/3VobwXs9bypTJGgtbButuz1e1QRALofvguNrP5vMZrH/1cyrM0E+NvRBSeypYLyPGfHFvIIIebFbSh0I4EYT2SRBesq1hYzawwr1k032bP4CpBrjxkf4UmgvPdzJ+AbLfy3BU2d98fuze05WUC7pxUWmoK6kMwYYVDnnF8y0cyz0P+cfrACC4htwDEsYySNvyFghVBB2LQGs35Xgtg2F9T3fvqUrKwm7R782B8iaVrTovK4Bq8YsZ6Wm2KeB0LGCB5Z8i3wxLtyyvBLLVMhsf05vuowlQHvteTdH4yiJThsvx6vDdT12X9IHbR/YPVUZt1T7GVdlAxEoYw3JbwKWu4XI6AS5goXFH5HzdgCxi4WEYYwoVw4Zod7drNhpu9zDhKk5UH0r4BY75DvIjuuYV6ksJc7WBTm9iNWBVC01Cu8YN8BIjyhWw9ctdkE/Wx3BgrpZJ78qW35dho3pXNlMVxpDrfTFW+jgeH8Sy3cUtQSu5IB+1G5WxNbNYweFyESG3brpcZ8PrEIQXfz+uuXLCgirbcG9Ch2tsaHiJYTgu+5nar2LpRda3gmd6oMKiPr58T5UfkVSOBWx3JY8K1BUUmBbawM278qOB0FjchIzp36Lo9Z58Ekn3bT4A4JMIGFd0pgqdOXDGLzRDzeMXIhxVYX+GyunaV6qkSN8OsJht0C9DKE9am96xB7rcFPADDf+37ElbF1RWqB6cfR/n526CUCsu6LygYwFo7aabr0NgWP8b7V2hklLoICTa6DygywzZhjAQABuSlzFkYx9+ycbDqUpKw2XDZZEu20Pxthppv8kgYo6vLd+wLFuMGMYdwfVkWuw00TeZQn62MtEgyKJqb1mFh+1g3u8BKKEEZQxCPjvwSCxBmXRABc4dkM8QjLFVdvuN09bCEEPvS7BRXRg1JS56aEGVuNsdjy1pK/32N1un+v2WB9aFVuLwClIpfHM1QyGPbYrbb5q/RX5j00oWGt6qWkfRhPFaupFiFVzaTrNBcNy+n4X03eqFZdYLEUR9WP4LEnSUSCT3QGOZ6B2vT8DHwHAvz7YfqF7nvqqop8WjBm3jI+T3z5OztSt+kyqp3RSP0VkR7kpjtqQyhCqWdNubh+mkXfuEAt/av9nfu7bskhF0oV98YYalaTRjMUDUBCz8/EDrbqrbK6kMap+QvgmVlPGtuge+DdlwULprAFnerjzd8LgS1DR8tifnsdtlETcy5Hg9+gmAiNlOjETTb/JJFQVE1ekAh1MN1+YCh/2aJkdHs9xq6Q2DLFLAxhCaQMwJsZ2t/c6Ztw8l3BOLDXFMxzP2phpYx1yj8rsByKcXVvrlLsgnGvEeYC7JZBW68vsybFQ7jk6fbmGBBTF14+FnWb/6fbmSWnIlpVviNA85he0v/opa+T7IrRufdhz7kwsHP4QXnzssYwofK7FYVVws9+NwXNfPZH27EFS30Lf8SOlj94+/Mj0pKqSfBOGlkwZGCaTjCOIl0TCt/IUpUgVJmhHoGIdF8U/blXVmyWv5xTPlpEjVf7qSMi6D91UhQ8faWHldKkO0bXQY19MWsmwJf/geW+LtZnQ9tYDFo+13nG7Xx0kQA4elK93TvByo/LJBtwZ0LACtj949MSEwrFKQ+KFs6cxJnXFxD/aoaci7xVNhMLINWx/g6PxsvaIOyasrKQ/I1jqaqIU7Y5mrR7za44h6ZRE1KkLxssTd//l52z4anKx7bmaEBa7UYMO6KMqxZRSlcMBJxOZIFG2sWfkldpAhkEVOmT6WAee0dJdQJ1hVWOa+ACX8659BEkWQqMm9s1pSTQcFBiCfBlbZg5XeB/kMwRi7CucrOyPhHfl9WQ5dGIGee6AK+gjrzJ6TavWJ8djxtu9rh+z2pHCuC3U6nm6hujZQbvjwtu9+iWH6oZV2+L50070ADFjPFeHQi7YNH3TIS+QfheNSvBbcU9a3m8Gta0Efuz+1/ksF7LMgvFWuFgSMQB8tZucPTNN5q05qVfOMeM/YNeD3j8iJi0bmsxXg4dPSHw/h4TxyAUVRwH7rrO6zbCCVIRXl9QgQBHxtzrDEuZbxAi7Uu+H7LiCY9cIgYVtHRhcksL+wxt7SNsXyrA86/kHNA/WA1j4FBMGwvhfse5wHee64gCLPYeOs7nPzlmxDywdC6a44f3vLTA/IloDXlxpOOTZe+8BcTo2aB/WVRboMv1tP2j59EDGetIFD+mOEmF8bOKr1ETj8GEFVQEYnojKsMxpPATFrpEjTQ7gNWaSEKegi7l+x35e+uxBJDSUMQRllyKcMK70P8ilDam1X1N/ttPE9+X1JDj0Mhe9fz3tIFDh2pOzCCye6rS873vZ97nXSyaHYQrOGQBHai915PTQ33WCLfjjkUafX/fTDgC8wR9ljfcR7zZT58Rz+qFq9d8FxLZgnxd+5lvVtpx/fs6+9+rDCDUFHJTu6ummvGzosD/Wh6wXbfvScyqTZtl0J2JG3WLVnj40nZEtcXPGInFz4+4d/tcy+YdRxMqOpAHrG0pVUhuCcMi+E0H6XwI5qRhkQbIOE81+3Pm/rgnqeIx4GR1n0UBGBUCXQMchAa51m+zNUBtnP9b8z30/nM/4cQWqOqnfLVgjacGi6Q/LaIFssX2JTDowhHkVA5YVtT5WoIWVRKN6+bshYAnAb4FLoleDsL8liT0PFZp8UgwF1FrKDfw5k0Q7R/e6DEoagjDgEKIFV5ffuhHy+FcYovh+QozlAlih6OCqJzpWJYB1q8rrKDF4zLNflUw6BPAaDxQUu1TAYMBfOb4XjeqQR9e151tzy68P8rPzM1Rf/HrBjG8CTv0l+z/e/tpxiGaJs446s+fI9KewJxBRJFrl86Jvqnmf7b997J2TDYWGF5O2CbG/5PVYmw8uiULyS5BKImBbLIRzcchZTSUmB4f0XZDGknWf+xqtfcJFDmqo9T/Hyq+1Uf2bKdFg/KjiuFvr1+dLAT04Dn6csGlRJYe32gix+kJdeK8i3G1itVrDNSzM89EGxv380Pyo47vur4xXDSwOfVgOfpCwaWEl9WjW+BHtp4KWBlwZeGviGNeBUUldomqYzHvgNp/2VtJcGHtfAE+ZN7or8o+OThPssckjyfbb7L3292SKqkkJYJO7R0KtwIoinK1DbNdpILntaVYS7ph/ZH3SzAAAgAElEQVT6G0BO5pVHE+/G04fivPclizDdW4GFYanFDKnWgXoe+Xqf96+BYr02/MOPlvMhCrNlh3eR9w3he0nz7+gH3vjeRSnhQG05zF6+8Cs//l+f5Cffir5wa4JePfyIcburFYeFEOF8026K+3FGMN/kcLqc4bBf8nLlybI9Oh4xN6sERm8i+Q4gJ192MI5SaBfiDkvI056yCNM+2m+5jGGUbdvorE2N7c1P9u1akH0La8XMx0n4IIXZssO7yPqG8L2k+Xf0A29876KUcKC2HPbqq/BbP/Jfn+Qn34q+uvvV7retSPYPBBVdj4jMiWDJ/H3zaH1YQZIu4EQFm0UWjhOYr/am8vLSpG9Spv8sUrL/a76EqUXpNQKpLxKhfDAt2A0QN8Zq8rhDmNYkd+ojKdovE3oTSDSZ3SmcJBI7ok/Ws5Qp5OkM5lkM2YrpAxL91yMqETjy9ZzCQXL9bJ3z4oqmBD+RvoaVAtXicRaHi0MU3xxRAbAkEv4EYqQPHxQjzytAA974Bcr0YApzwA4ohqTX4URy2c7YUJOI564KRNL8QD+Q5bXyGNpV5TExPtw4Xrb0dyR7Zwv/0TpM6n8bef5f/Iv/0eyxQ8J+A355Af3QIdZnkwQWixkkSB+PU1jtD7BfZkS7TtIZ5OqMKik9oRMAEB22mWcQxxM6yWG61GWT7KeuTd1rqTx4i580IMgj5luWSvL74eXdc+O1K6lQuXXYzMneE7T9eglpPIWygQ7ZX7K3a4/ouEJ0TRbsuYhkYYkmXSs6tkvdtijTEiXbFdC+1hSDBKnKAvH6FiXZDo+/y4RpjWupQlRkq3CSSewBkrwmn3vov31ZNQ16BMt9CcecN7/x0Qm8YzvyEOnP+ZJwO4vdAeo/t88R7bj4A/EBo8kM8uMRdopkv+bWSU8EJhF44tdA390BzkdFvE62MJjCrGkbRF0uYB7z0DNvZOad8QmSzo85TGmTM3IMeXf/KFvD6XyCDY0IjIE2dfYkl+0sk8R7gRAjDXfG90jzg/xAllfKY8hG88anWvhRtoLydIL9mrE7CK91/zS+6i3k+dV3/3dHjl/OxoTawgoHR15wqmA8zw0zE/1QE+tR/iiKYVMUsMrwPTzzbAl5vuYwkRgeSI+W33cCgP8khbOipnv81FVO7/p9/OQ3CzxexSOPRR/vnSRxkPxelwMR3CrvxPz6YLymkgqUW1XBVJlstYeyYBujP+CQp6GuB+ztmiQibpSFYnEf0MdH+MjCX06I4u/TtX/z23/nvX+wKNMYj4+S3YvfuqFRLWVVQ1XVcDlwLxALVBzrvElJ9kwbGTilztudwkajiAK0X+t5wpv4SOzf/wNh6G3wZZdZ5af/WklXX5l3OJ7toW4qqOoa9sQanENlKMbM3tKsLYTT4vcxAmYxjeY57i3dIpl3ZQjEL1Kmh1GYQ3YQ9VoMJ9yHwg9RqLvpxyshPUP8QJJXZXhfHrtI8dHy4D2cyaYNnA9rqiiwUsfNlXWt/jX6eBSL/fcIed6WIySv41+tv7FfXgmi3Mpi5igC6WHbtXlEn6pQiycp/IHYft580jdo5877+Ekg3xh99fOt7Pf1wPLu+fHqSorXDrQ2sanlVBZP1gYsXNOxN0w40e9DwN6u/0Z6oUK/9VlBkRdw+WeZLPyL/+inaw+iTJNr9CnZHY9xLnyoFmyVYcY0iad3BEqyp5IKEaZp4YSiM4u0X6twMhlOy60ccP53f0tzfDZYUZ9IqZEu2BXWf5r+q6/NZ51Ty5NRK+0il2iygNrIoRJpriuqmLCSoslbc5+fu00yN7ETYJRbxVbc2CrG+GnITPHnqOU8Jmabgaeq83W6dmpRRSE7iHotKqgGEu5D4Yco1Fbq1VeBj2j0WnXwS/SS9gNJXrWgyG7EsLxYCAjxqeFVe7ET+sWi+BMfTUM2QDvN4U94NIZBnLUNlbvI8xqCi3YMyatGS+YauW/0wv5mKgHlprY/hIn8nhMAFDtu7kxVIAhX9tO+Re077+InIXkc/dig15Df23pzMVFGx18CenhjvKwnP7VcN8C1Xo081JMaA1HX7/Df6KoOJptq8qUKudrz8MH6H38jkoX/RKDItlXEJ3ROYbv7117qtk2Zxmh8lGydMN8nGkYilLtGm1tsL1tJbrhcEVlpsAjTbSUVoP0aY3NFGXlJ7P9IZPdpe/wqgTBHcw3yteK36L+urMjamyJ8V60sxOnC+nyAfX6EqyUHvWdf03cVh32fQLXcNd/hvMAVQ2ygzHdQ0HlergSB+EXKtC5kwxTmkB3I7l69Difch8IPUahdDYiVrqXXu+X91f8r5rGLXTlY0FnduPAR7KtTCYeyhLI8QHnSJxK8kTxvy6FWvNmNLkMbt/TQ80Pjby03UOfbUHrIdlYl2+ZL7in0T1L4lZxP+gbt3HkfPwnkm4C+ZD/CAzHbwh590l/evV+8hv9oGtcttdyV2zxrVVIhe7v+S6v7mBw8gjkefFhdoNyp1X0ExNTk2j5ZuJFo0hc/ddumTOv5JZeS3fEY52I48dpvNO8y0ABhmpXLBz+KZHaLBq1p38seiR0gRJLHVp+P/uskny53GbaOE9ifamiqkiq/CIcYLTnoQftaHbGw2JdQ/9CSvum5AMn8nvhlynRFh5dF6QpOeKYPNjSiFAqXwhywg6xXmSzfkz0QPss0pUVCOBmcEeA3Bf8xDrrSdUjzlr7vl7cS6d2NXTlYlRQXpn6CvZt2bqRF8CbyfEeOQJlg6YHkcK51g1HnRV3YhtLTVkqcsvZaOElhfQQxnyBWeb+C5U5YP/xOfiLK4+hH91JxdEj2o4F09BpkPbw13gC1XM/N40nD5+OOTmBo56S4cg3Z2/Vf3idFB7y1Z//gsME4XbYof5EsDOClSdPBcB7qtiHt/kGkZIfWleHqmi5VeQRz5WzdrnF3uE93TftDmqwOiaxOilQtOJH2q5wanQp7IXu18ICH5MawovsYj0CSx61XAv3XNRZdN0ezqIDiGKe8OsroVo9tl+QcSKTHHtgMjy3HAxT/Pqf7LK9K/0FPbvIzk+lG5gVK8Qco04MozKghgfQd0us9RHIp/BBJvG8DgTQ/0A9EecU8JsQXINi7MuuK4U3keXWum9kjI8kr+KH2N50X9fB2m2+HE/ntfCmdpODej3Q+UTT8aJq7ajLX7+EnojyCvjjfyuVJqzcUO1DeSfn1CfGGyq3jdqZWg44gjnGL05QW57Vyy/Y2hlBfusSJK5J4ZZq1RBbGygPf6+8FkO67Ytx5/RDx+lYcEmG6fW8o7bf/3BCSPOqqS/9tY+5/Q1tUtelr9x/w3Gn6BrKeYlvVwWfax6X4+2nnd4ZTmGU7SGFjJYa6G6YOKXy+PzD5rSIC3x6RV85j/ojo+RtCc6H+DuR5bJbRAo37/NCfEr47JD2+91mO/kZAvO/mk/NuCuNAJaUkEU5aeJuf+OTxpce+J/uR/VT4+/vF2y+3jpspJLOd4Y6eNgjL5vMEXSnJbjf8t1tJuSG8rp+mgRdJ/mmqfAV0pwZe5PmuwvLlHPY9nE73mdfV4xrAM8F4lCeBlHpREaRr3hP6SKivSuoRrT30zosk/5DaXi+9XQMv8vzbdfgK4S4NNOcStusVrNYbYRHW8OBeldRwXb2efGngpYGXBl4a+GANvCqpD1b4K7qXBroaeJ080NXH6+qlga4GIlr5EyJOdJ//eldVQXtJcPmyXhkUFsYif6vllrxiJvzWR/z6uM6vsEkn4EvH42G+NcWWnt8alHq/XQH0tgCRUDJZHMzmU5/e7BjseAeR2y3yud4Ur/ew2uH6vw88ecD/8sfdbY6wWmyJ1WmvqkPd0ko/pYPlpz4F4J3UZenmnhiM7u54yc7fj7x/R1T+R5204uITnHfanORFM3YesvOWPwL5riJOzM1KDPnRr/lLA+tkBONsAYtsPIzE3iF/D6Cvf2DyGA3jX+0SFKPJicG3V6vM7WcfDtMO5JHvHT0/EkD/nUdIyf1QADTVA5fo7pYL2AcyFL7fxjuQ3G5vxLyL3j/85AFfuj7y3vWAS4m5fLBPBdD7mzQhYSHt7/hIYT84Lls390RNupvz5vah75k9m3qv3J3vD41Heq6b1goWkwgyhFOLf9081OYt8QXxh4haR1EKy8WUKMJxksLaULADBN0HSccScTtMOq4hX80ASc/4b6op7EgQHsdtbU7XE1iVX3rk71mcwlYVUsfdEtIkZgpztoCywqWrw0nYpM27yOEAmgqMFGha8aJ7r4qurtMWa7q6z2TXI0zHY0Osl8JEQvJoHEOSxJBMN1BLcRCB+S2Eag9h3WuPGpjEnUCWJhBP/v/2zmfllSVJ7PVEegMvtPZCL1C7AYE3Q4HBg7yUV4KBtjAMwhvNRmZA3gjuIHtAfbmamWtx26J7ZF/UM4hGc0HHoIUOqBe10CJMRGRkZmVlpKr06Tv/Wh+coyqpKjMyIjKzMivzF2wLkf8ZpGRSl5Dm8x7kxRAGPYSebgHJ3L797+Ubkttxj8tk0Lf+Z23kdVKXO/R+35ytIw94VHSijDehiqNtMWLBeAj9Xg/yvA/TlTQquq/7vvNnf/4X8G8MXqnTn8H5sIBisKBRld9J0WZ01DfqPe/DcLox3LZ0Pr18AIM+1+nBZAm7zdyTVTbbKrR1hbrv69keq+2E+GUBo2FB9u0XY1jvNjAucughWX4c3zNY7t0+UNbNHPKe799/VMn6OBLKekMYDfqURzGcg+wP1cjg3E7zg+1u3IMsx0gKfD9Gq5CBbIpMbvVhD9L2kTYk9ANkJs76OcwNzBhxVhQdAtvn/gi2lxuEdQiXpQ/NCj81csZ5S/WM0sJoDNsTScrTfeiI+Ri2uw1v+uzwngpS5h1ybyvSsVDTI8RtGs6SHBMnh2nIU3J0cYOqbJj1Go2Q/C3XYWOJw9QcSep7Q+vO53AmCGIGuEv6eNjCpJ8R7ywyaMHtt63I4VEqMJXtBkvMJ+vDcneAvaFCd3GK6s6fnqYjJBfjMYyn/wjfaXkYptxbCNWankl8zx7Wvv0hjEdT2P74XFIy5rce4abBHiy2e1hPC7Jzjzoppmygn0T1FhCaq+T2i24jr3x3zFX5+U2RB5razF7Xg+X+CJsZ6wMblhT1netaBuw7v4Z/ID3msNyd4OOWR1VYJ/xOKqeOrAtI8V4ZvSP0uUk+9yjeGh0e+XzILRwH1P2KouXE2CnWTji/nMJ2uzCvFDIYztewnjGLMkaWx9E5gwWMbnbsz5n49w+8mTXWngiDdDDbwN5EMqCHqQQZvNJJTRi8UExXsFtzJAS+37BQG0ZUaGKfmB/cBMOEmDfFDtU6hBinDmQj3ECtRMi46LKbTsrRbEuiFCMSpglB1/T/pkIIIFMjHaeI2+wsnhwIxaQNYGk5sPOR3ewy9UDnAflbrsPK5cM2Mb7PdLGF82ELy9WengDL6wW286Jynfg7fqbK4V8nx5SnR0cnzhmRLBJ0dblZ+dTTxE6qC4RKonsTeTS0W4pYHBLWRc+UtdeIs30N5FZ2/b+BlFxXC3PKBpZBybRy5CP6foFz49m9fH3iN6T1VylvXajoN2+JPHBuajNznePrMZUA9ZGivld9B30d4bQTeh3gN5R+J4UjKan7Pn0/mQ/aoS/BQxlvNVxzeyLtx8Y0XFE6vErdj6jc80P61TuP++XMjATPxAC0nVuQdFU32Ek5/25edgwmi53OGC4JMrive/JhqzuA9SAjaCtPCbo2FDe5TzoZUB0IZMfTpIyVNqTqBxVWoGqHeLQAxuHVI2dsvv8VRc4QXJYvu5nu8wnDRtkPEXTTpGOBCtJGLzONgMe9yRbYCL4cppNqRBA24x1TMamTIkcMyd9MqM6KpcXIW9sRGgpjvjAaiD5lSs5exAepcgSX0ilVaGwszZ8LNQAUn6ig+EguX3r6l4uVz1SatgGR/I4riOZhK2vabpiMRqjmDqCuZ8raswfbtzBBNAHeRkqOjG8Nn9A2ltgRTgyE05bz0jDfKp+vCQFfMVP0a1lkUX+Ncz/ywCagjEsjKws2rO1tmQ1uHEc/ow4TqBO+bu83kvuNo39srwvzsecYIuYEs0G8Ttn7KZ8q1seW6YMegWGDHEgz0uE6K9T9iMp9mfDnhF9WX/BX5QpT9vUR+neq7DscVQzWNjkeGPBUnlbP/LyqugsjCcTJ5DYz/6CxfcC0z/Ie3Wejanao1iGRWYuQEeKyUEzxV+6kKoRh7qS218cIupi4dTJTP0RA/j6DGHGbjFCRQ0ZSCTnCVXu+M9JxnfyNssiTIcp6Oy5hMJjC6q8QfIpD9yNcb7ggbKSOpFLl8H1AjinPnjydmbRplJigq8vNyqeepjcVQ/cm8vD1lbCbdMox4rZ0UhSrKmGP0L4kv0c254a7GnMmmW9NL1xON3LwOkKvnE3yJRZaF99n4bRrc/3VRFK+eEvkARxJ+aM3ra7Z0aPtCc3IcrTlkbbi66gfCaWA4vt2izaUgTw23+2lRT5+o+e1H+edTodXqfsRpbf0S1f+qlxhyjXdeO0XjUgVHdNIaOg6KcEGfTBR0mP1LKp7I5DYzNYhu+DOkclD2fE8JaOkKff5Za2MpFQ7SCdVjX7AnZEf9eEMs+EQvvvuL4PIGU52M5KSHtI5CA67HiH3YqGk4sjQzRbYQDgxkuq5vMF5ayJPLo5BT20qh+E9qXIIhX20hEt5gdWIn9poJKWQvy9b7PwyinV0K08wxfc13QkHD0QIIkasuEfCTpRDjOp/Wprx5gQlgjlx5ISjNCN/f8aGPG14XrvJSEpN039fgEKk8jCVV6ZLNbtxBVGI276eS0O/j9jDr2TsI2z7Z5GSceEL0/wL2F5KOO/4xTbN1XvlbEJoRhgwTpMQuf3yewLyRm3kpevbG18Mj0czB2j2f6RjkfWByANBnprNZLSA75oP1xKOK+P3Ow7zQMDPiK/bumpk5oavD5tTCXzMbYW9LpDHp3jjNc3yqXYGrkyip3oEBp26X1O2rQMUaSBoJ0K/tOWiZKpyhSlXdGNfT/BVqbLLO/b5/gLleUsBUTvDtWkD4/XMl7Mqo/dQmiCTh7LjeUrGMA+/rH4nVZp3cZMNLnIoYUMRiAdw8uuQiX5Anb+02cMlXG4l7Bf83g8jZGjRIJSRVI9DcLck6EpjFw7d/CE0UtNRGJlWE+I2GcF7Eqmca3JgdN8Fr9en9PKC0uY9Gxr5OySp92F1LKEdCZvp77FyxJwBG9D1uEqZp04KHcW80GZ95NWVf/HEzLd6mr6+yRm1PAISsm63FLHY0/PmotqjYk9TgmeSkinJcg9DQ3tHfeKIgzr8oJz38wXwye2qjSrkc1MofEijByEXM8n94h3RVEvVJxpFHgjKotrMTGlJPcPPYsrk75Svh76DHDbUI84ybH7jgifa6wJ5MAw8hrXBPWnN86lOq0mZaBCo0dYT1H1Py/ZQaydCv7TlojurctnEzIGmG/w5WXZqyF0bmOUTMw2u1zNfzqqMbroP802RyUP5kzIGI2q/rLvS10sJy5Hvxx3gDqtah3yZtcgZmuyNiBOPEHRDhVTP2xG35V5VjltJ4eTlOv9TJX8bknqVm9yWcNyuHEwztmNxK+ZbKMdamjZxc/CWPCStFLG4oueEPSStZ5OSJV38xIUvGhG9Tb4+uf0Z+vNltMcPRx6wKcQPzDTcZIeRmWOE+Ba+frtBSQEx41mlv22RTyIh8r2IUVvZpYFfJkSI/5TUzZ2yYxsUKVOqnsWFCL+tk8nDK9z5HRndhRQUVfMDzQ5+HfKTSkfOqEaDaNRJVRN/nb008HYNPJuU3FSiz5VvU/medl25pSXafjTop6X9SuilgU+ogVcn9QmV/cqqqoFnkpKrKafPPle+aame/esNDtsNHGij+rPTfqX30sCn08Crk/p0un7l9NLASwMvDbw00FIDr06qpcJel7808NLASwNfjAaS78S+GCnfJMirk3qT+u7fjMtNicR9/9LnXhFQi9+cuFlqfI8k3iafz6abNkI+4dovq5zPp9Y/QUXRJPwVYZULDHn9zb54OxJRIisW9c39lQzdiSqTu4SWYm/nc8vTq/z0xhM//7PZspJlHZiNqvvb3piNvf28mUK304XBdAHTIoeJIOjsFW87aFI3Xp3U23R8925H4r576VMvqFKLn5F0M5J4m5w+l27ayPiMa7+ocr4Dtf4ZOoqloZKzDeNOtrzE7m383WUNvawLqwjEJJaGKpN/8Tvq2M8fqS3YwZ4uF/jD9zOYrQXK6wvzluMSFoMCpqs1zIZ96PXHYJiyb0m0cm+TukGd1Hm3IBox0mf7w6l9AkCSbTNScSXf6gnuBxkVkCOJeTCCybAPA6ThJsjEmIAmUzXx+pl2HzL6CqI0I3W5D1PafAagfa+Sr+tZVr9JkLiRSj0aDUgXo8UBNOIxE8ObkJnjFOMaoXk/g7w/I3o1Cotokp4596nXREwX+dFeBZKWcxjM2F6OJB7Pt6qIyJmkHVLK6VKddh1JyX7Vlqgc0tgXP/w3orIPB+ijOdHTXUiPx2RCJM4cfT5SzqTN+yOYTU00ghyjEUjLeYHFeEDp9Xo5DKdrtqVKZ9/DoFfAfDmDggjoOQyITB5Q65EI05LmL4p/SO+R8t1OK8i7fUBWKf+VsBz2oJjtac+dkLOvhxUMMXJBjnR/b9N+2+gFko29D+n2TG+fbYVFbi+qHeAWBpKJIgi8TcfkixGdYKZauyT572d9u9c0Hy3hZ5EL9++fNjCiaANYrgHMTbk038P81MgQ8zEU/T4URQFF4dLCDe+r6ZDaMvTJkUSmqGks+CJRNzRfzBj4l0EfqeDHraGgjwgdj0Mx3AR4j1QciFE53RCZOofl/mBJzBw+wZGp6QYPr5KSqZJ4cKLfx4gOJF0cT0dYDJGW3QXalNbNoP7943TyFImbN//2gMjxP214U/NgBvvjEdZz3pSMxGXecZ9B1k+TmXWKcUBoNvRqobgR8gmBloRGYRsz7XgD3xuS+Hy7h41ho4X20vMNDBKcqroBAJV2HaRRPW1PVHa6ZRr7P/2GKR+d/hT2xx1MctxkyQzJx2RK0NiTlGuWAzd22mgEhh25IXJDF6brHewMOWKw+tcknV18Dcnkywk3aIvjDSrU+ls7mr/T/Rv0XivfCQYYlWBuwogYqjZuyHfk7CNRGVA3u8MWxmQjBks/6ouP3mdlspule0R/f0TH1hdrOtHaK6REME0ceZJo485gCtv9EX66Sxnfq+3NI5Ehnl43hI4eiZCRcUdUwP5ypQ2x592MOiZE7eP8511SsbR8zoO9o5BMbXhMAZmabvA6qZRMXuK1Q/2+jzBGzE0+gjWy+a5nOB7PUBrkfP37BPm6lqv/RVjeKokbnUpIzymyuMPCcNpkB8v+c2TmFMW4SmgWDiKnR7vXDXKqQr2+MS7fh7RaEKxnn1S+vjaqxwndmHyjtOtqIpWzR4jKoW7lnNiDmLppJOeHn6lhbCsTQKqcF9gs13DC/dxlCafdnMNNbC/mwcQRrB2EmHf392YSCwpjk01hsf0Ah80KNgd81LjB9byHsY2fxYgZa8fbjhooonl70QHa0vxF+Y/rPVY+gN20ZzmZpwWGFOGHBEHz1Gz0Zl9ME8ClnLFPkUmwU2/RMZcrphPGMdXbJQ+BVCH1u+812+zOZ9X3CI/k0X7uRoZ4sL6m6kbKFzOJbeLjU/AY53utQchaPgrD8fmEvhwzKFZ4H4aJ18TI1HSvRyZOyRTNx3yZuu+yc7FisHw4RMb+VfteJV+nBGhE4na9epp47Ijh/stSgp92TAytBMXY74j8YxTfP6/Y2MjvQ1rtnLHXMKQIz6p6UroxizJshacpSWT7uQocS/cRojKX3emWzr0KKo3P6Nffk++2lUl83r/P+nyCJs9yRaIAGNbZeOf8RnSh+qi1lbnHniN9AmcwmFovAN+w7mNUgtTf43qPlA8zOi3pwXh9ucAMO1oTT018kzFJBtWG1/sopkQdSJXhIR/2uZhWp4/rWLV5ol0SnTgIMttKvtdsg7rQ2ht6CG4TGeLB+pqqGylfzLBwSAWn5zEKUHuGzWpNmwCl4GzsKmzRPt3U647nG0yQHpg4MfgDQkApvkm4WswanTtHTSYv8dqhXpaPcNhu4VTiE+cBVjOeWhvj02j0+59pCqJTTOFwQs2UMM/1uCxOkGYkbrxejKISj72GU7NDimLsN77MkhuRjTFvme5D01XT5qkXn1Jg7eXZJ5Wv00V4lNJNgnYdJuOdc+PVjqjs6wWT4oYiBztOMeWc/fwbncDtyVA/1MvZxuYsF8JcOZ5aseQopZjfcTmG8XKt+6hnK5LPP6dj1hnX4XhUgnq53DfP07uArQ0xuxhAJ+vA8sSwMvFN1oVnZzMyxAfpx3wxTQB3Ja0fiUzc2Sux7BrqOO6LqJOr0i4xHJgp7UIZDzspfLjzdAVMGV/+8Nf0IBBrb7BMrSJDmNWV/sMsxcjL+DVRXWvyjV43Ur6YXTZMRx4t91DerrDG0MRZButL2IDFOykhnYsY4ScTzAewOzsyNUM/dWJ2SqYwff9cv4/z6gzN6GnP0Xmn+98RDLP2/f/l76Pkaz/D2rFQm9MkbryNK9594jFeaysG5efsQM6lkNt9ajE3Kkx+L887atws4DYASco7xNX+CLsl+wbZyzxUyAhbo1vXVGK/SOjGEszrtOs66dAm6OjWLYjKrvHndKRyFLMtlLcLLIdI7i7g+KhM9r66D7SxuZPzZqIRDGhBU3la0Qgv/5tfN6eze7aTp9nJeg/XP+6pI45FJfC0XD98gGTtyiN6r05Bn5ZMwxa/xKus3xuQbw/p+thGmXdsj/sip93ehz2ZfJ2isP65mTW4p2NdJ1p7db+TkqgH3aBOfPcPqO94eyORIaa0wOIMU3znl4wMIXW5ZX1N1A1cSIcRnmO+mOF8NodBFipvB8YrXsqoThnaJv0AACAASURBVDPZ6Zicael1N3bfIME8RqZOEsx1mVzCsSP9vtN6QvP/MrWRj1YUbVT7XiVfx7L1v2tI4sb5WX5Jz3rv9pngnk/33IF5IynNDimKcZVafIFZgYtFTF4SKgSnX4NOClftzCVQXSeHQt5zeFMsqXx9VdSONd3ghSrtupZK5Yu2RGVqGDzdyoxAD99Zkn66MN+b6YEHZcIKF6Wxt7B5RU5cxWcWC6CMvcGMFjapPurZipTlkcnR70amPuKTsBaVoKLkyMnb9e6I6pS8CTMxWLpl1L5vXrYzV3+7PeqocXHFo7746H1WpifouGJjeXA1vqm1SzZ/M7tDi5qCehy3jd7eUB/gR0roFvcjQzy9buiRJdw+KUMFTz65Rpy16VdI9sVBvH3HITemyMSPyqTex8TfOng4/r1G9hXRU58pErd/39uJxwmKcbAbnUnSVe67LwtOay4GfeAnKvzlCtMehqbmEA/htddLlVZc/V0/S+mGZWzrhUyjL2tFu0+D5oZiQu8nsTy1JPCB7HqFa91p9AKaX7RyPmbzC4yoE8VYPe7vUR+tUOtx4cUFyfGx0ru86keP672eVpNv2NfrUibqQDLZR+9LJmp/fLuOWb4HXI8X01wuEJo05XuHGc+izTConv1L6+jZdUPo6L4vuk7KCvW+B9thBtkw1ui9b76v1JtpYGu2HfRwZEejiy6saDlas/u/tquuW3w/6d7Xfany7+cj6OEIOOvDvm0f/qUW6iXXF6MB3FuZ97iTejPJ48ml+uSdFC5f3tKy2SeX5JXckzRwg+N2BfPZDOaLNRyv/lPVk7L4kpK5HmGzPURHUF+UmKcDbLc7OH3r9viSlP6nJMv1BLvtFvZHXCj2Zf198k7qyyr+S5qXBl4aeGngpYEvWQOvTupLts5LtpcGXhp4Xw0E723fN7MvKPWvqNytOikkOshqkrbqDleytL3/813/9VCjQx25lUDhL6/zp2nALD3+0ubxn1O+r9f3m5S/QhH/z4+3bZjXeevRwgfPp4U3KU/Ta/xyp7YQnXdLmBvGadO03+O6Vp2U3bfwgCQIPZzM1rTs+4HbP98t70g0fu9C+cTk987rTzf959PhvxhdfsW+30SHPkX8x1+9JdRFnRYuuxiayPGpr/HLHa7+c7KUMMHVpOOd++ozHWUhFXp5/Aib+djRbecb27H4nVRbom55WEAxWBgSt0LQVcnCqB2dvN2c1l7Gy6bmW6dG385bmAz6gMT4vD+AxVYWBOPObvweKes5FOOVKWvcshqpWEv/LcRklMBSpHs9GIynRJSemZp03MyhyHMqE1Hw74Qc10jz8ZIqBG+Noky26MNkMoJ+jrosYLbewXo6YPmKEWzOqcUcim/FhYNn+I6jwwM8S5f7+QDywQTG6Guoh8KFSWBbsg8OJzMY93NAWyISR6Pdq1T/p/h+XLkpn9N8qEbl10jv8SzJnp0uktJzIKo/xOt8SBH/0d8vGCXD32A1yqHbn9IeNdyegfsJe8Ml77fcLmBY9KHf78NgNIODXeASzx/FR0wRtSNo3/4Itsl6p6cTVYWit7DcpaIftIPsqywWyGPR61WbcqT8Wmv7Mtlxn/WZCv23/wWXIXZgut7DYTOjTXO9KfemtpNK0Jw1ou5HQ+LGtSMqQTdBFk5Rixkse5/WztdFypbIt0KNLhnAmnWHsDnsYTnOyZCzfQnHBZKmc1gdTrA3pGoCekY96JkU6fvEZNyFXuBTEVGkdzDp88Ze3LF/3SFGJYP+ZAmHwwaGtMzZMdZC8XXSfHgln8cJ3qcGPpDDYruF2QAJEBg3ZwqbzZzJzwgoVv5U31Kuf4bvIJ8Sbf1MXYpcxXQF2/WUNrLmGDIFGC2DhPz9kaGyqB+ypUq7T1D9n+D7UdUmfC7lQ7bc4zGMp/8I32HMpKwPy90B9sb+wvaL5Vu9fwO/pS0V9Tpfp4jLSEonw98MY7A/xzAiCMLNCOGUsjvLU88fyR8dtNtqB6fDmutnfxkrEn2nphO9Q7d3WG5dP2smQBRT2J2uen19qBwZ1Pxa/CXStppOioGT2FsiLbw7WsO1vMDlipgk5DpxWAfXSek0Z7wGrxeknxB1P+4MBiVF0DUVxsI5PXpziryN717u09oTZUvkCx41mlFDPvS0hEmHmX7sRF2YLrdwvl7hfDyCfZgKHEkjFW++/1UAVXXp88OEy9unZMcJ7w7hwnJ3YSP7azyWG9mrO7WjZVt5FHIwlzNOzQ+KSZuBUT81gvdPP+mE8cAWtz2GsHAssuR7tpRv1YWjb57hOwJRfqYuSa7CNVrbUYc2VQshw1Hb19zYUSdZRQ3Re2Ci3Seo/oG+0d+R1h8S01O+H1NtyudSPkQsPuuPCbljmRqAdWbvT9R5hSKeonFjloc5d07YQQ0WTMfQ7f6L3p5e2G7FZAH70wUupyMcz9JqhoVLlSO8Fs9TeuPIDF2axkul612XqletysGEmyzm11vGNrl3ZK7ty9iRDRX6amIc0c52wcRkkPV4Rz4ag+GG7Ym6tsKYF822I7KIpQ5szhxjaiwNpNeYpqjFvlwVSjihRkwj9yFRNpuPcRJ7HlCj9zjqyCubKbnx2ALcjnaEQk/+vSFslE2wGqmYGXvx9Fl/boRj9dmAmFxSQ+/uxYcRpBdgQ1Rr9E2jhU/msb8Uab52vUbwbuEDtlE2pqnaOsgxla5S/6vpKaT/Rr7zXF1W5XL4KobUuocVMHF4eCSndVIAbyamp3w/MAOeJn1uwjMQVE+8tkZYfNLGUDrHFRQ0unftEbEkI3niVxW9JdszBdB64FBFoWyODG9mJbIe4LgW/9Q69Pd/xzGcvDJy24DtKb6+cFNq+CA20SLrJsthhAg+VHuDV+5kuv513C5H2+xri3KE9vF0l2r7uJOyIx+OhdM3Achw5v962sF6w5sdxQFSNGe8JkbU/ZffmgqUIuj6nQMq3TtP0Y5FLraTA7DiuWvkEmXz8qE0/HM6NtRo6u3dUz0+sWBoAcQGXY472B2vcCvPsFvPeagcxQlhBY6Tir/77i8rowY/feqUrJ0EUNuMmMwdmoyW8UGLn5alUcjyudvMasseb9XFvtiF3dBBbo6az/r3/+cntRrBe/G3pJ8oRdnmz52ksx+nW7W1nxf6S3uaejW9t/kO6eZJuqzK5RpfGaHYkdSNwZw83Yd1zNEzHO2epwijVP9A336dk7AemFctX8/3AyvQ6V2faxR5ISF3LNNaI5io835j7d3H/qaT4XdT18HmJqSJbvd/hiFOpcfa0+sJtjvEGJdw2m9gUjDY+BB93ZoqR0wRKb15nY+JfRaVz+pnl65Xrcrh/FikFj9P+ZcZSbnpOaaW92F9vEJ52RtiNk8H2QRp6i5N1MWnglt5ginOKXcn8IEaeMwnQdA1T8L2Kd47J0dQiN8iFxc83tDgMFItm5cPpeGf+0TjjxxMrks05hIO5t0TBjLcIO4pK2CHLz/LAzmn/0QoRqHPp1KkmxCTTWRTCj1ygPnAvZM6rzlsyRTtdTvDgijg1dGcL7tOmvevkmNH8N6eS7geDcF7/nsK2ZJlEYqyr3vvIUOmAaq2lnzkM+FbcknwWU3vbb7zTF1W5fIqtwGbMuW6SgRXaffG36JU/0DfKs074fuBSs2p7nMpH6qUOyV3PNPqSAoSdd42wtVQFykat7xLw0CYYuv5obTHsTqktTkfdxyJeUJLvEvY0LuzKpfRL6KWjszg+9cKCT1q76DceroXepWRFTM4Xku1vrYtR8W+3sMB+h1OM8fa1mAkhU+jBxuemYam3cKupnLD2jtE3ambt8WXnqtjWSV7awTdBFk4RS12cqGpqlM2MozcoTW1siXyDanR5y0vJpHpgP5kzaOQyxYG/rREdwi7+IwZ+VOcVIz7LeLpR0dSjYnJALfTGvqG9N0xcvLDQGlDH3CZujBTpvq4Iuik+UpFkZNA552CCd4q9TywhdhPeHVVW0sm3qfmW94l/mE1vbf6zvN0WZWrOqV03c9pQZP4IH5OyGY67f4ZxHTNN319+se6z+k+FJZbldvPyDsO71fr/B2KODaYot/ecAEXOMMY600+M+/brzCjkBZjwBjfEj6kVocC/89se1rCcuRGZbhYjTssrzD+oZqOf5E71vXGsfHsftdEuhsTEoUA02q9aleO0D7+ueZf6j4ppNte7uB3U0RdMCTy6OjV6LI9QTdN5HUmSh81KVuYQp1oHCeAtyvTMynSCWJyuYNBf+TepZ1X9LJ9fnTPYa1p2ippPtQcn7Ne6t7QTl/xtGPfvme69+rFe+vSaJTJ7KWbuhU9aLpuLZdJsKnvS/702cDnpI1wXlhJwZ48KrdNAJ9PG7Rn/vU41d6WDJ+SU8s/dU9VHj7T0old2yZtLd1bWbpXAUaPsYgAbfKKyeq+Q71X21a1k3I3vY6+fg3wnDa+nC0KXCqPT4RTG6n36y/fn3AJzBJgWo33Ranh5XNflDm+YmFendRXbLxWot9w28ACZrMZLDd7t+S8VSKvi788DZSw327hfG848jkEf/nc59D6N5fnq5P65kzavkA4pK9O6bRP47Pe8RXBMj+rnl6ZvzTwFWqg1knREswu74tqXR6zUuitsM03yWCE9l/ItS5HixveL58SVuM+dLp9mC2m0O8O3DulFvKlLj1tZpDbsOm4H24Aq2N86Xkqnda/maXigmVqe7+vcx+WORu5fXxt0/yTvP7N9dX56HQxg37v+T76sF3Me9fCLP+mdMoDzCZLWvgQLkR6OB9zY1sY63GBe6Q6RKyI5f1s+WJ5pL7DDdd2cYW58J7Mfnp+HfW/f+S41knxDn+3JL1dos+Bbb5NBpb4U8FV3y2fcgdFPoDlegGDvAeD6XOjGcsy4N5wBrvjCU6IROrhiqYurM/trN766nBvTssEfJ37sMw/fD+DmbYhsmUefxqXv7G+oo/2BrBcsY8W003lJfvn1OF+mkNn4IgdKMttN4IsG9NU93OB121hrBcYdTIYJSrac+Vrb4lwqTgBAO7I7Ofi11H/+0eOqZPaLcYW5lnkHdrXxM/Tcaghwge7xdyij+C6g6Kbw/KffwcC26yDa9OT5qoMCijxXmEPiyEM53vcOQuDXjNgaQqaK/L1MK35FIp8SCObaj4FzJczKBA+m+fUsfB6Nh2Oi8ZfjAeQ5z2C0w6na9ZreYTZsIB+v4CiKKAYTEDIyhqI8Z5O3O+82a87Dju+I0yKAmZb7qU0WGpTKCv5SV5A0TfQ3dGc4ZxBJxWFjZZ7GHa7bEMU/IxL6Lsw2ZxBdB7CMn8Wm2ODdNrAqOgTKDnPBzA3ZdJszP5awGhYkO36xRjWuw2Mi5wAr4MxLkPmP00viAArcrZ9nvdh2ijMge4bWnra9+hLq+nQwaFnxpc0fZR7W19xNdt2NqKyo++i/OIHqo/CBdazMRR9BKsWMFlsvDbhAFMCLhsQ806efNqBmFHjYpvhoIAcAc7FENZmZSr6WAUoa9oLBkCjXGOqNxgeHfFVuGio05/BOQBeR+tgQp/GFegDZZDl6gxjjbebeHGl7hZDC6gO28vFD/+9AuSOypdoG9tAX/2yyLHfSWky47V320XN90JdVGDdIgV/ZpctbyobzNaw3zLAEzffYifFjK06HFGIEyvjd6cl7osq4GgaH0a0cLoCrj0k+ihdBh2UWC1G/Ww77kCGxAeD+UGcURJYmoDmRuXLeoAbTOv59GC+2cHS7DFYHG+QguPGAaz/CksNrJkAMda1oHwjGzh3+tTefWhmU6BvBsP5Fg67hdmsxzYR3p1skOyPl3A4bmGEo7nOiDoz7oQ6sDoeYYrfd3FPitN5CMv8SWxuUEECAuYNyl3YXvaMqRnMYH88wnrOG5lnB9zHJ/46he12QUQMbHiG8zWsDb6Gr9OAvLyTvzOYw/F0hMUQN0x3gfbnKWbAr3Xf0NLTvk+AmzV9GAwZ1lddDoC4jwaQ4BVDcPnBR4e0tgMxs+LENh2C6u5ggvuTMsZ8cRuVQXEXSHuFDe3fzGG5O0EFeI2UnKwL0/UOdmaDPm7YbQorLo9VGKvWblrQcwSiKmWU9vKffuRRHz4YxfWfaCNaQl9j7mk7qUR706hd1HzvosO6Q3kyFMYBGQHOq4EBxKbgg+yE+QwR7iU1IB0kU3tPyKx0D8UT5uyd6zKkQIleApFDq+QAoKkCS2kl0hoIt1eWcNrNLbgT51eznkMHXTfoQF1AxKCWj6CHqAE4bGG52tNUSHm9wBYhlbQRlzeP1gCs2w9w2Kxgc0AXvcH1zLRrnCNmfIjPbnMgxoga4l+Zd0KFPGVErgpt4oNnSR+W2MzEC6Ru4J/oFzvw6nUAxzluXhzD1fMTrtAasPYCE5qCxEapZ6chrc4VSKgG8N2dz7BZxm0c+ivbfGamr85EEEFb6nr5QDDRLB/BeneE6/UMxyNu80z/6eBkpl/U01O+T0BAPxzn9P5jLUPB2wnmkxnsPvxEowvc1J2Soy0k+BdD1p9uz7zX6LIjoDBGU2B7NwMxi+bENhYFZRph3OfXBkhLUObOhGzC2CbGirUt3/lWwvV6Nf/Qwh6MNQHp/iUBUZUyClnlrnyJNgJaQl9Fz/6n1LFUe9OkXdTqYgqmjXuurH7LG1AnRR2MkdDStZPwQYD9LIesM4WLdRjEAQkgFsMWIEfMgGv90keOSSFe+AUrA5q/JWBSkhclO5l41CDOIAxbe52J74L4fBm64yfu5Mf3Hr6O/DTs/bbsZnRizy849wSzAYZA8dLG0aoGYE2UOyQwYHkt5FYKf+9TUE+1kRQ+FGxgfy51aKZpqB3yqUpp8HVDTjx0U4oMHe3D4Y/OT+4Ba0uq2Bl0BitbKqvzAPEi32sAX0wAp0FiNg79FWWPlbH6PRqKcS7U0O/cCAxtnY/4Jb0VPHag+UYCHHyJ5WNGxzEI6A//G6Gp/FBVEeEtPprK73cJSGsLELPISrbxuJWic2Q/is3l2lR74Rp+j32p1cFE+X69xodUqcv4wOjx8BLt5jkB6Q39z8qqyZdoI3jq1k1Bou1VeK0oLvgUvabamybtolYX9XT/nh/2rH7H3EllPXliRJAkDzOvSfggviNAakEHBtj4mlAerkMwnZTvWIES/FNUSFyGFCjRT6F+LEr2ZcKr/EYUz+U6mcIcLjDURrXDJfk8cKiFIQYjKZnCImm8BkCH4yoA1uWamIkxIKjN2z6iO8htXQvaN2d2hGJRfdFt6AUYrycss9Pj1eqMU4/z7vAhIOykThSDpzqSonwU2CgSvglFQw7bAeSk4Z/YjBBY3cyuQpLvuQL4IGB8DzKE5Q9/TY1LzMZhQyhphWUkeT1fcHr5AIftFk4ljnwPsJrxVKIl+nNCtf9137gq6Sn5/Pi/VGjvLwrQePXPP9qRlC6H4qMJSPAfzNTpCoNTEoW4hP1mBdvDpRWIWZTFDXYOOG9Df6Zu4fRr1U7p9sK3se0EzMinDQT5w/UE+90e9vs97PYHuN6kk8K4ezoM9mMCUO3LhmW8K1+ijYCW0Fej1cqH6DXV3oR1wV7rtYtaXUzBtC9H1Cvqdwf74wUyASXiS94S+UzIpzLvpHT4IJanZHaVR/n14ZROyZWyR09UGR4ATEoGomRfJvxNOikZVst1LG8cmivvZ0aLLZwOK+hToynvpMwTt7znEe6dd07GjMJxHYAVF0WUJwNg/ZtfUx5RQGQCxIhE8sV4bF8qiy5in2eassygN5rD4XSurO5D3VibRMCzojNON95J0XQfQTO7sNhfoDxvYYDL3QdLuHm6kVWGo+UeyhvGL+MRJ05NMXG6B9vrlUaz8h7C5S+NQwAJNX7DENYS9rTcN4Pv/gFH95qNDaXfKMvlgV+4Mup60UG/Mf3Ld7pvaOn9jnyjM+RR2mWPU3kZTPcXFQJaKvpY/eJGtLocio+mIMElk9nx/dy5vMF5a97jLY7tQMxGSVxnMyhmWyhvF1gSBLkAjOZUsdOd9oIb0T6F0OFjBl5zO8ew40YQZDGe/fRhrKKvCKQ7UXfD9vKufIk2okzAa3HV3XTFcbCs+JEDq9ekzGzXZLuY8D0NKBuKk+HQcG0izNohrOyTSsAHMaHzCp8Wu+DmuvdUgXDqg5TecCSVkkEHJYZFqZ7baZnGwNIUNBfgsJQhfgdyXAGJnY4XDwWCfOQc94yl4LgIwOQXwTx90BswgDVVbg3EKE/1+O6kyd8unPrq9KlD4Xt1aKbVLV1Yne6TYTwuGJCX2tavemM44nJH04gx4DYOG70dF9T4SmA5nGdHp8botC7/KizTfQ8QB/jqNg791U+rCi3W9XJaTypTiflodfedVMo3tPS071VoL00dutVtaI/hYo8vEF193S/s6jf8vT/ExVBmH4/io/fyq0NaUZB2IGZ0MXmw7Nk9fV2Ym6WuVTsBpOoN+hSv8Mth85uxC84atHN3IciRylWBsQbpOajsYwDpEJIr8ull1aGvqK/Mm4KPFIW+8vWqtjcYBPJeu6j5HvYfCkw7lMnuk2JAoJ1DqlynwQcrFz3hRJPhefDC+0JiWa9lFYSKS577XoPDK5Ta7iVLwXE5CCGGrjh5IqbLXQcxere2OGSQpgZNTcuQzgafxjgC6I1hqKnLWwJrU0m537hsgTkJNhra2N3T7EjXSwL0qyad8g0tPe17hqnGIKC0COdygVAfTqyUHHEfxXupzkRh1Kz/mK71e5w0csQPELziGOGj1dopV7lP3Ta4sucGJU1BuuvliGWqp95U1hiMNV6vHqu7MflSZY39dloNodugkxKduM+6zO3axXhdZJ+sAmVdnnxkO6nwh9e504A81WfdPtA+siyDAvdgPelvPx9Bj8Jn9J9OlXiSiA8lsx1ljZ7aHkr8ddMn1cDn9NHrFmdsXDDHT1rwbyyzzXQM61O9I36kmO/dLopMr05KNHHnszztYTmfwWy+oBfAdy5v9fP1dIDtdgcnXLDxDf3hsmZ8Wf76+/o18Fl99HqEzZajg3/9mvy2SvCe7aJo6tVJiSZeny8NvDTw0sBLA1+cBhp1UkjI/rae8T+HHW5x0vitTLwjaC/nTXnh8FVTztur4XXHSwNP1oD+LuvJGb2SCzSQ7qSuW9opjqt9etPEO5h3pAsH8n5Rp7h6LSQFxwW80RLqmA55R3YO+yc8BVzW2tw9793AzY+vv+dqoC39+rm5Pyk1syXARS8oYVHgClYJS/94Pv4qscdTeexOWhUoK5UfS8LeRei3fGHP3+sA25TeBPdbfeI/rw1/Ss41n3o81WQndSNqRB82xzOkXpe8H1348YJ9ijvtXoI7mfEeiD4clI5oWeACg/WdVO78bPYjjGsUCb6P2Wy8t+ROSq+fG2ugLf26ccKf+MIqDf24HELWKWBGG5L7hP96VKBn0rDbyiB7jeJrltukdoNFnoG/4bfN3W2u3U980kmbO992rd+Gvy0lubvqU/LtI5+0TypGP0acBe8p6EC3NyBQZoxWrdGFL6cV5N0+uIf3EpbDHhQzJJMfYDLoO+KyIRVjAZrQe1W6Nq7J3y+gIIozk7cHkzXtVQkpw8vjHxPUZ1+VOh3a76S0fJGaMKINz7yBri5HCXBe0lPr0gB7NbJwSm+7aY8YjARlQvJ73ofRaEBE7NEC9+rzfibcZ9SGDF8hIFdIxQ1o1kaO8XgIfSLD92G6stwAiPkT+cB8APlgAuNBnwjkeTEGARRr/qHpXwjaTejmbeWp0691Crkmt+9pdHyN0cNvsBrl0O1PmSIPV5gPetAbLuHjYQ55r4AYIRw33G/mY0dFn29431boH/P/6dHQcf+Kq0N9pO+bAfg+YReNlC7EeiybZiOsIzMiphta/njlaOqegjQdaj4qD4eT8YAiDOT9gd3oXqOna7rC/G8HyHHPGNXPhE4bRlvwikTItPkIyfs9orsPeoagEtpocVD119zH421ZrQ3fzyDvz6wNsC/omfOa3pADifJj/S5GMB7kMDBtjETEwGXmsT4G9aAT/Z2WMpV+XJ5hTdTgAlbbA1wIUplBnVat0YVPhPbJJeiYYfzRzniN8N2Q3iubRGt07QTJXHatC2V4+wNvzsXd0sfDFiYok+CdnH6SdGjbSSXyRXwUbopcmYoeysGNL6NnsAPRycIpIjx3QP2F2Uluye89GI9HMDebew/IW8zGcLG/3yPD66TiRjRrm08PlvsjbGa4QTQjvFGKfi72LaYr2K6Zrk2dq+YfCf07fafp5o/IE9KvVWq2JrfnZ3yo08NvJ36Q6c/3cCC8VEYB86R8OiG8HsUAN33zRlvjHz9+Tw+kuAnc6mFSp9KrdlFJ3ScXJSBho0a+pOkwQel2upnA7mAI+1F6+gZ+S3SUiK5o7zmSFXgJPOsgcp3V6Z06Fdh8PcJp1R4stnvT3mbQM7Duio1+2ryZ4K+29RBvwyVGgqDysAmzPkDU+Q18b+Sfb/ewMdEC6BWIQVcRYNvQbeptrU7099WU6fRjAAG94nCZhYvTquN0YcTaMNcPC8vcNsTrJ8jmDem9tGvaUrg9unaCZM4O66jsqXL7Ckpd5zqpi07XFl6XsXgoB+d1I6RNZ7Rh3l2UuJ7Qm6modqrPVBghk0t52J4j20kJjFTI5UKZlvcIPF0SJ66zP9yhWRs53Lsw7kwR1pvyJ7Jv4QLWMUB3AyrduYXdKW3LqnR084fk8enXCQr5WfPrgKZdJujhaMMD0vMNeFNIHOJPYjuh1c+P/4/4jN3RGq7lBS5XRE51+UEs9I8KZxKxVPF6rtrFjNLrNP+zwxYlbNTIlxQdpny0ppvLmvSH8P8qPT0V8YGvxbqJo8VxJ4O0TvlpVKtTUhf5k98VD2w0AqapS0QJ7KRsHU7oT8opqDfNx1NtmdaGo5w8ImV4QUVvxuelHcFrLXTW8yk9X4XoX1USZCqhuyYcPoUL+dd9WgQShmAI7gHz9Le+XGCGw1jzQlAnFeOw8D69l4zgSM1AOAAAECRJREFU7Zq2dO1bc8p1qtwVHSUo1baTukvXdhsR2eB1OrzMRVsjGyHEARHYqurNvKS0oTesg8izECcmaW1MHCGBn8r3IRleEEd7b1LfEteb0Kwjcsj9Kfq5r1eUHO3NRHLdP3Aq6E1084nu37o8HjvQ2MCvsKw/7OTjcvMTqtSlDvyQooeTCc3INuuBLGMif/LxY/Jg8Ou/M6MlSd989iZeqBTjH9ZOF3jILon3ob7uNBtBE1+iKaN625Dy0bpudqSTGj09QS6/mo6JHgBT11kdsk61OmWqtamQGxrB+j6DnQD5epAe3qDpL2xTXH3Bu/jBkFBpibaM04i04UGb7tsTH4jwlZB7CAWQdkwQbYQ+S+QbJfpXlASQ6fTjag+KwmUKrdp3Br+wpCCkVBcDIqYvaadzglTckN4bdlJC1z4fOERAE8p1qty+jlLXicFSBHV+0nNhEnxduXx49R86J+nZo2y7+xN6k0ZCehnr4GaO0WQkI6lz8LtWoWzetpNyxPXLcQe74xVu5Rl26zkRuPlp05XKOqqN/GeeFKWcij+JXiUle674x8+/b253mxYl7sCxpPe28thQITucdlAp5GdF7t9/rNK0P/yWAy/G6OEoLgN3ubPJJwzV5foWI4T/gWJg9c10O67ZuZ52sN4c4BbY39pJ4mW11oNCSl8e7EgqVUca+ZKiw3/6CcHAPvHe+SjrxlssZKYMp/uQns4jmqiuaATXM8ErE9cFOtXqlPg0f3Kd9ht5+5AapJfSX9imaD6easv8NLjeew/WNjJGAPQFfqUzdAsPeEYoiC2o56uR/qsP1xz0MErornZSKVo1FyqkC7MZTkvz9CNLQU2DGiN8p+i9vnFleiCka3+k1YjNKdcEicVoAkLozoraCjxqvBT9iDNwZYjny++kgk7KjDpdmfhpB4NIqsT1C1OxY3qTpyW7+sg81TPA1eVC76TwvVvwu1QomS6QciFBHqccuqMlXG4lHEzUUpyC2AyxsSxgd8GwJgdqEF38JZOnearP8jEcriUczf241DnlTzZ/k4yca/7xLy3t7uR0ndQj8uD0DwbMy4oZHK+lSiH/mKBSO+s48G6MHi7vijBirJDYMXQJ2y5OCFejGAT29yMFPKYHIX+HJHHXSaXqSBNf0mx/Svio6KY/3RA9fTHA9z8RejoAaLr6BYPA9mYWFKxdVwY6VetUxeA8zY8ybS8lnHcMAaZ3OrX03k7wx3qktXl+G86j04xiUJXnHa0tkMgYUhelGBt6J5XDan+E3RJlNO/UPPn1fDXS/xXK0wbG4xkcS4AsRWH2e1dcocHhl2X6oANjg3xX6cJYEuNEg6XDwz9C7xWl4Cd3UiJHBpnQtaE55TpVbj+v1HVuWK3ni6Tp3JtbrurU5GQMOjHzahpZWNcbwBo7DRmBeXRrVxYmhtNoJ/g9nDJx5UqQipvQrKWT8qaJi6kEQdT9yc+f7G2n+zS6s67/UN/VtL2pkIR/V+/xpx8BKvRrDHVjIwmjX44Mi1GT21lHjpDezi/M2b97wwVcJK5WLiuurhwmpzsGjt3UhRghPKRnWxp3YH+fhp6q5yk9hHkJqdvdo9uoGRld16FG05ZOqmvp6T1YKPT0UH7R1bKfQT53bZd2XVWHuIAWF1vklsXp9CCWNp/lHoaez+D0GS2cCG3Uom2r5uV8PNWW+W34rrzAzOyTw06n64VvqqaNZbjQSlN6FdTJoZDViZ78qXw1oj8/1GSAD85mn1SKfhwq9QqXy9U+WdhfE3Rhe413ECP0ys+p3/Aa7JlTdG2iBSvkBcmDP5uWu9l1Wr40gulO6zozwhwwrHqHKc/3yMKqbuj9X8eFTakWlIJUoiPZd7Th78nzOgFZLk8Sos2UxWR3QVQ2REHZD9DPNR1o+hdZG30+JE9ZIbJoOtHkrsvFxOgYPTy8ljvhNCEc5YnTuMPUvPMH9IB3c9mVDYHyu1I3Nb15UoGuQ91HhbStS+VyCHV1u0baOlOO1jp12dSOyuslXj+CK0lHiv6CS5XTRFsWtOH3bIlbHBaDPky3Zu8MXGHay6A27U+SJPIF/q3SPtDghqdZk5t5lVJ+9q+/Oro27bPIwK6+8zVoRlqy2/8tZGGaivDCrLtszLTCWzcMuwSbHZVbWszgz1k3u/F1VVMNvAjhTTX1uu49NLClpfsZ9PqFGc13YXWyL7EfzrI8LGCy5D2VX2UnhUsavza69nW/gvnamzYw5sO518XabXDFrx8mC5dHmM/WdhOe85AzLGcLDjjovvwERzc4bDdwwPdWr7/30cCLEP4+en2l2lADNzhuVzCfzWC+WMMxhSZqmGJ42VfZSYWFeJ2/NPDSwEsDLw18mxr4ojupT01f/9T5aS71pcihyff6/qWBlwZeGvhUGvgyOymPvv5v/9N/pF3yuHIeV/U1o463VJ+SX8tU3n65J0eMmP72DP5EUpDVkgpsV7Rw3kyh2+nCYLqAaZHDxOCj5Pc2n+Eqwjb3trn2PfN5pj7alCl17TdBmU8V8PXbXQ18kZ2UT1+//OsGJjOGxIZr9O+WruEFWn4Nb3/aZb4c7zC1+zQ5v/yEmhCYcWVSAdPVmuGmfQexfaR8t5Pz00fub3rP++XzXH00LU/6um+FMp8u5evXtAaokzqsplD0c+j1esDUY37RfdzMiShO3w+nsDcvwEMS7u/mA+jmBaWR5zkUo7mhNfNGWSSeYxpIIV5sT0mJQvr6b35eQDFY0GIAv5PSyMcponKsPKn8cE+ERmuvFOJB2revxz/7838P/4b2EznqfExezNe/rz9cAOq/lw9g0Bfy+xJ2m7lHHhfwrFIelL9XwHw5g4Jo5TkMphu7rFrzD40aXtFNcIKN7KjoMzU5H8DcLF/V7QmgUeFVKne5r1C94/LfYDsfQ9HvQ1EUUBROFtz7sZoOHT08uhilWjBcjSR+ivZ5kz1we+FhBUNTJwfjKR3P9lfw81HLnySOA7yfPhRCeFVVehSEgPz9H/7i31kUW0Ek/4bph/m9zr9qDWSIecf9M/l4CYf9moMc5nP4aGCXfaQhHzYwxA1dSYJwBnUquU7RVrUW0Nc/GCQHAn5sJ5UgH2tEZSE51Mqj5peijgfS202rD9K+kSj8X5fwvUed//CA/gfzNWzmGPgQbZXDYrOBKW3KG8IZEuXx5J9vdrCc9CmNxfEGmn+UKhU/0E3l1FC+u0PYHPawGOIO+C5sL7qf6FR4t6m7Rks3+7OQV6bJf1bJzAAqzbxSlupJjBT9sD3Ev3Okd+9g0ucAhMTJ9OqDbGqvlT9BHH9PfbA8EUJ4RVXN/BDp/bPv/pZxW8UUdqer2cR/L/1KZq+Tb0ADjEXyAJUY32O62MJPiNDwN6AKKn+LzlL9DXchZxEq+QcigMcp2indMWNuTJtfeecxgw+lk2KERzxdrih1Ojfeq5Unnl+KOl7C9Xo1/0qQ0AeOwcW7vO/SvgM9+nKk5E3rn1EjQk8WGjNCTg+bFWwO2N3f4Hrew1h2h5tOyoIubwbEaVlurH+0mfgHhzaI07I12zLax9twjLFoJjPYfP8rCmciWCbcJIi4IdIf2i1KhWfyQxajpXvcM9JjxL/Phy0sV3saLeJGyi0SxvG6FM1cK1gA4azWh/b2YP/uwka2m3jl8esD5RMrf4KY/X76SBDCK3pr4oeyOZRZj7xxv2n6lcxeJ9+ABjJx9HAnC37vGGfYOjHHDZ/m0NH93yiNCJX85/9TRYOgvoSCndKdXxH9Y8k3RI5U0lWIyqny+Hn4xxp1PKRXh1RxX542VGk/75S8ogfRYfXcYVDwd2GIJSnqthGMULGxkyiWdupP8kyVS64JP3FqlUZOVX5kDSGD94mfWOCmScwvT7XcHq7IlufCoU8i8qsUfLPownbY6PqEuPEfisKSVTmXVbna24Op/hjWRv4uFDgTR4a+j1Tz8cqfIGZTXX0PfaQI4VIM86nVKwe6FQfxKfMmnpKH2KIZA6S6B+m/Tr8tDZiR1MQie27HJQwGU/gfv+o6FhyW2Vb8691OSqjkPJKKE4pTavQron8slVKeNG0MHXDkY42ojPdatl1QHj8Pd6xTx2/XKr36+sctIevHb6R9u7x5alOTV/QgOqyeO2gq/u4adb08zraGmm5tzQ8kiGySh/qKfyi0bJEr/OTG3vcHjMg6hO+++0uVZB3azdr+6k3/moysHhrIv/ornGrMYbk7Ai5SoQcPHEmlaOZhgbzz0HbuIa69PTgtF/sMzMiWpvsIpludWRAxpPwpYjbpM2LPt+sjQQgXAemzhR/6lHlomn4ls9fJN6CB7EJTcky8vZUnmGKE2u4E/rDmdxvT9RFut7N5f8DARKkMUn6ZYgup5LcEoRifZOfjsQ3nLGnhp1/huVEKKmUiXY2oLOToWHmi+SVo7b6sdCzvdN5I+/blSMkb6r96Hm8UNymKukcspvJ455p//LJh4vFouYfyhgH1MFheRuxAn2Bc0ZXRaXfIVPX9ggn5q1902rq8S8SonqfDCvr0JN0j8GS13F6nFZGf+WJnmObs3xQAMEq3FzI1E73L0xYGCCjN59RRn9YzmBqwsl+2qJ+yMilQHsXz8R4akvaAI78bLqZwOB1gTvTuDPidFOo9qA9GENEH+1Gcyi/2fJY+fB2ohHD/olS98uzGt/iUeSGt92F9vEJ52Rs6NzMx0S6TpUTZ8jN8HX/tGsjq1OM+rJCPDiWszQt0fhHfhZnZRxJORckLXL7Op5InKNqG6yaV11ckVTLzHsE/9vPVyMc6UVkvj5+Hf5yijvvyylSoLX+WwSO0bz/vVvqvTL9Wp5dkahQHeWp5PGIxlcucM08wpJWLf4TfOyo+lSNjgnFFT7jqzIQjEF0NF9ywqPbE1YzLkVkM0oE8x0UEQ8D1ir4/YD72vFKemw1bT3l2C/LvFJkZVJo555F5U9tSPt92Vg768QF74FvD0xr6ht7doUVLppPCkZSpG9V8vPIniNlU32cuwi/SvrG+P6oPKT99lgcY40OATMl1C9icwxcJLfwQw9KbNoigpYn0sYPGzrsaQa0i3evkK9WA2ydlqMehS+nUYVdidJAUlVwoxFV4b0nRet8GH9XJxxpRuUl5XMkgQV32rjLTS8+mfWMObeX1pIoePpye4h9IN69R8T2CcVQIXLhxuUDVH6i0cEXCvueE96jw8fTr3x5mPNKbHb3EDX3Zz8+/M+ZDp9UQupFOyr+vzXHUHuUOBn0J8wFEsMeow3N6eGyeeoqY/Sx9xKTBfO8RwqPljiVGdaBOmb+XvpLU6+uvUAOuk3qD8A9RyW8HmI4xVs438PeifVeM6BOMKz88cPIWKrxkV+7ntOcJn/CFNi+/tf3cTMewpgjTbe9scz2/f8FFJkXB2wGyfPq0uvJMfbQp1evalwYe0cBTOqmvkUr+iLL0e160b103b//lYSq8ZH09wW67hf3xK3okomXkC5jNZrDc7O3CFSnSmz6/Rn28qcCvm79mDTylk/qaFfCS/aWBlwZeGnhp4MvVwP8H9UBIOmv5YfEAAAAASUVORK5CYII=" alt="" />